Packaging material for power storage device, and power storage device using the same

By using polyamide film or polyester film within a specific heat shrinkage range as the base material layer, and combining easy-to-adhesive treatment layer, adhesive layer, anti-corrosion treatment layer and sealant layer, the adhesion problem of the packaging materials for power storage devices in deep stamping and high-temperature electrolyte environments is solved, and a higher molding depth and long-term adhesion are achieved.

CN114696014BActive Publication Date: 2025-03-28TOPPAN HOLDINGS INC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202210322936.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2015-03-03
Filing Date
2016-03-02
Publication Date
2025-03-28
Estimated Expiration
2036-03-02

AI Technical Summary

Technical Problem

The existing packaging materials for power storage devices are prone to fracture of the adhesive layer and the metal foil layer during deep stamping forming, and the adhesion between the substrate layer and the metal foil layer is reduced under high temperature and electrolyte environment, resulting in leakage of electrolyte in the battery and corrosion of the metal foil layer.

Method used

A base material layer consisting of a polyamide film having a hot water shrinkage of less than 5% and a heat shrinkage of 180°C in 4% to 16% or a polyester film having a hot water shrinkage of less than 5% and a heat shrinkage of 180°C in 10% to 25% and a heat shrinkage of 180°C in 10%, and an easy bonding treatment layer, an adhesive layer, an anti-corrosion treatment layer and a sealant layer are provided thereon to improve deep stamping moldability and adhesion.

Benefits of technology

The forming depth of deep stamping is improved, the bonding layer and metal foil layer are avoided, and the adhesion between the substrate layer and the metal foil layer is maintained for a long time in high temperature and electrolyte environment, so as to prevent electrolyte leakage and corrosion of the metal foil layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114696014B_ABST
    Figure CN114696014B_ABST
Patent Text Reader

Abstract

A packaging material for a storage device, having a structure in which at least a substrate layer, an adhesive layer, a metal foil layer, a sealant adhesive layer and a sealant layer are stacked in sequence, and also includes an easy-bonding treatment layer arranged between the substrate layer and the adhesive layer, and a first and a second anti-corrosion treatment layer arranged on both sides of the metal foil layer, wherein only the adhesive layer is stacked between the easy-bonding treatment layer and the first anti-corrosion treatment layer, and only the sealant adhesive layer is stacked between the second anti-corrosion treatment layer and the sealant layer, and the substrate layer is a layer composed of a polyester film having a hot water shrinkage rate of less than 5% at 95°C and a thermal shrinkage rate of 10% to 25% at 180°C.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present application is a divisional application of application No. 2016800125362, filed on March 2, 2016, and entitled “Packaging material for power storage device, and power storage device using the same”. Technical Field

[0002] The present invention relates to a packaging material for a power storage device and a power storage device using the packaging material. Background Art

[0003] As a power storage device, secondary batteries such as (for example) lithium ion batteries, nickel-metal hydride batteries and lead storage batteries, and electrochemical capacitors such as double-layer capacitors are known. Due to the miniaturization of portable devices or the limitation of installation space, further miniaturization of power storage devices is required, and lithium ion batteries with high energy density have attracted much attention. As the packaging material used for lithium ion batteries, metal cans are currently used, but multilayer films that are lightweight, have high heat dissipation and can be produced at low cost are gradually used.

[0004] In lithium-ion batteries using the above-mentioned multilayer film as a packaging material, in order to prevent moisture from penetrating into the interior, a packaging material including an aluminum foil layer is used to cover the battery contents (positive electrode, separator, negative electrode, electrolyte, etc.). Lithium-ion batteries using this structure are called "aluminum laminated lithium-ion batteries."

[0005] As for aluminum laminated lithium-ion batteries, for example, there is known an embossed lithium-ion battery in which a recess is formed on a portion of a packaging material by cold forming, the battery contents are accommodated in the recess, the remaining portion of the packaging material is folded back, and the peripheral portion is sealed by heat sealing (for example, see Patent Document 1). In such a lithium-ion battery, the deeper the recess formed by cold forming, the more battery contents can be accommodated, so the energy density can be further improved.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2013-101765 Summary of the invention

[0009] Problems to be solved by the invention

[0010] However, when deep drawing is performed on a conventional packaging material for a power storage device to form a deep recess, the adhesive layer and the metal foil layer may break. Therefore, it is required to improve the deep drawing formability of the packaging material.

[0011] In addition, in the manufacturing process of the packaging material, a lamination step of stacking multiple layers and a drying step of an adhesive for bonding the layers are sometimes required. However, due to the heating during lamination or drying, the substrate layer sometimes undergoes thermal shrinkage, and the adhesion between the substrate layer and the metal foil layer is reduced. The reduction in the adhesion between the substrate layer and the metal foil layer caused by heat is not only likely to occur in a high temperature environment during lamination or drying, but also in hot water or a high temperature and high humidity environment.

[0012] Furthermore, during the manufacturing process of the battery, the electrolyte in the battery may leak out. At this time, the leaked electrolyte adheres to the surrounding batteries, and the surrounding batteries are exposed to the electrolyte atmosphere due to the leaked electrolyte, so the metal foil layer may be corroded. When the packaging material is exposed to the electrolyte in this way, the adhesion between the base material layer and the metal foil layer may also be reduced.

[0013] Furthermore, when the packaging material is stored for a long time, due to the decrease in the adhesion between the substrate layer and the metal foil layer as described above, peeling may sometimes occur between the substrate layer and the metal foil layer. Therefore, the packaging material is required to have excellent adhesion that can suppress peeling between the substrate layer and the metal foil layer for a long time even when exposed to heat (high temperature, hot water, high temperature and high humidity) and / or electrolyte.

[0014] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a packaging material for a power storage device that can improve deep drawing formability while maintaining the adhesion between a base layer and a metal foil layer during battery manufacturing and use, and a power storage device using the same.

[0015] Means for solving problems

[0016] In order to achieve the above-mentioned purpose, the present invention provides a packaging material for a storage device, which has a structure in which at least a substrate layer, an adhesive layer, a metal foil layer, a sealant adhesive layer and a sealant layer are stacked in sequence, and the substrate layer is a layer composed of a polyamide film having a hot water shrinkage rate of less than 5% at 95°C and a thermal shrinkage rate of 4% to 16% at 180°C, or a layer composed of a polyester film having a hot water shrinkage rate of less than 5% at 95°C and a thermal shrinkage rate of 10% to 25% at 180°C.

[0017] According to the packaging material for the above-mentioned storage device, by having a base layer composed of a polyamide film or a polyester film having both a 95°C hot water shrinkage rate and a 180°C heat shrinkage rate within the above-mentioned specific ranges, it is possible to improve deep drawing formability and simultaneously maintain the closeness between the base layer and the metal foil layer during the manufacture and use of the battery. Therefore, according to the packaging material for the above-mentioned storage device, the forming depth can be increased without the occurrence of rupture of the adhesive layer and the metal foil layer, and at the same time, even when exposed to heat (high temperature, hot water, high temperature and high humidity) and / or electrolyte, it is possible to suppress the occurrence of peeling between the base layer and the metal foil layer for a long time.

[0018] The power storage device packaging material preferably further comprises an easy-adhesion treatment layer provided between the base layer and the adhesive layer, thereby further improving the adhesion between the base layer and the adhesive layer and further improving the deep drawing formability.

[0019] In the packaging material for the power storage device, the easy-adhesion treatment layer is preferably a layer containing at least one resin selected from the group consisting of polyester resin, acrylic resin, polyurethane resin, epoxy resin and acrylic graft polyester resin. This can further improve the adhesion between the base layer and the adhesive layer, and at the same time can further improve the deep drawing formability.

[0020] The packaging material for a power storage device preferably further comprises an anti-corrosion treatment layer provided on both surfaces of the metal foil layer. This can further improve the adhesion between the base material layer and the metal foil layer.

[0021] In the packaging material for a power storage device, the anti-corrosion treatment layer preferably contains: a rare earth element oxide; and phosphoric acid or a phosphate. This can further improve the adhesion between the base material layer and the metal foil layer.

[0022] In the above-mentioned packaging material for a power storage device, the above-mentioned rare earth element oxide is preferably cerium oxide. Thereby, the adhesion between the base material layer and the metal foil layer can be further improved.

[0023] The present invention further provides an electrical storage device comprising: a battery element including an electrode; a lead extending from the electrode; and a container for accommodating the battery element, wherein the container is formed by the packaging material for the electrical storage device of the present invention so that the sealant layer is on the inside. In the electrical storage device, since the packaging material for the electrical storage device of the present invention is used as a container for accommodating the battery element, a deep recess can be formed in the container without cracking. In addition, for the electrical storage device, even when the packaging material is exposed to heat and / or electrolyte, peeling between the base material layer and the metal foil layer can be suppressed for a long time.

[0024] Effects of the Invention

[0025] According to the present invention, there can be provided a power storage device packaging material capable of improving deep drawability while maintaining adhesion between a base layer and a metal foil layer during battery production and use, and a power storage device using the same. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] [ Figure 1 ] is a schematic cross-sectional view of a packaging material for a power storage device according to one embodiment of the present invention.

[0027] [ Figure 2 ] are figures showing an embossed packaging material obtained by using a packaging material for a storage device according to one embodiment of the present invention, (a) being a stereoscopic view thereof; and (b) being a longitudinal cross-sectional view along the bb line of the embossed packaging material shown in (a).

[0028] [ Figure 3 ] are stereoscopic views showing the steps of manufacturing a secondary battery using a packaging material for a storage device according to an embodiment of the present invention, wherein (a) shows a state of preparing the packaging material for a storage device; (b) shows a state of preparing the packaging material for a storage device processed into an embossed type and battery elements; (c) shows a state of folding a portion of the packaging material for a storage device and melting the end portions; and (d) shows a state of folding both sides of the folded portion upward. DETAILED DESCRIPTION

[0029] Hereinafter, preferred embodiments of the present invention will be described in detail with reference to the accompanying drawings. It should be noted that in the drawings, the same or corresponding parts are denoted by the same reference numerals and repeated descriptions are omitted.

[0030] [Electricity storage device packaging materials]

[0031] Figure 1 2 is a cross-sectional view schematically showing an embodiment of a packaging material for a power storage device according to the present invention. Figure 1As shown in , the packaging material (packaging material for power storage device) 10 of the present embodiment is a laminated body obtained by sequentially stacking a base material layer 11, an easy-adhesion treatment layer 12 provided on one side of the base material layer 11, an adhesive layer 13 provided on the side of the easy-adhesion treatment layer 12 opposite to the base material layer 11, a metal foil layer 14 provided on the side of the adhesive layer 13 opposite to the easy-adhesion treatment layer 12 and having anti-corrosion treatment layers 15a and 15b on both sides, a sealant adhesive layer 16 provided on the side of the metal foil layer 14 opposite to the adhesive layer 13, and a sealant layer 17 provided on the side of the sealant adhesive layer 16 opposite to the metal foil layer 14. Here, the anti-corrosion treatment layer 15a is provided on the side of the metal foil layer 14 on the adhesive layer 13 side, and the anti-corrosion treatment layer 15b is provided on the side of the metal foil layer 14 on the sealant adhesive layer 16 side. The base material layer 11 of the packaging material 10 is the outermost layer, and the sealant layer 17 is the innermost layer. That is, the packaging material 10 is used so that the base material layer 11 faces the outside of the power storage device and the sealant layer 17 faces the inside of the power storage device.

[0032] (Base material layer 11)

[0033] The base material layer 11 is a layer for imparting heat resistance in the pressurized heat welding step described later when manufacturing the power storage device and electrolyte resistance to the electrolyte leaked from other power storage devices to the packaging material 10, and for suppressing the generation of pinholes that may occur during processing or circulation. In addition, the base material layer 11 is a layer composed of a polyamide film having a 95°C hot water shrinkage rate of less than 5% and a 180°C heat shrinkage rate of 4% to 16%, or a layer composed of a polyester film having a 95°C hot water shrinkage rate of less than 5% and a 180°C heat shrinkage rate of 10% to 25%.

[0034] Here, the 95°C hot water shrinkage is a value measured by the following method. That is, the 95°C hot water shrinkage is calculated as follows: the substrate layer 11 is cut into a size of 10 cm long × 10 cm wide to obtain a test piece, and the test piece is immersed in hot water at 95°C for 30 minutes, and the dimensional change rate before and after immersion in the longitudinal and transverse directions (two orthogonal directions) of the test piece is calculated based on the following formula (I), and the dimensional change rate in the two directions is calculated as the average value of the dimensional change rate. It should be noted that the longitudinal and transverse directions of the test piece are respectively consistent with the MD direction (mechanical transmission direction) and TD direction (vertical direction of the MD direction) of the raw material (original and reverse) of the substrate layer. That is, when the substrate layer 11 is composed of a biaxially stretched film, the longitudinal and transverse directions of the test piece are respectively consistent with any one of the two stretching directions of the film.

[0035] In addition, the 180°C heat shrinkage rate is calculated as follows: the substrate layer 11 is cut into a size of 10 cm long × 10 cm wide to obtain a test piece, and the test piece is heated in an oven at 180°C for 30 minutes, and the dimensional change rate before and after heating in the longitudinal and transverse directions (two orthogonal directions) of the test piece is calculated based on the following formula (I), and the dimensional change rate in the two directions is calculated as the average value. It should be noted that the longitudinal and transverse directions of the test piece are the same as those in the case of the 95°C hot water shrinkage rate.

[0036] Dimensional change rate (%) = {(XY) / X}×100···(I)

[0037] [X: Dimensions before immersion in hot water or heating in an oven, Y: Dimensions after immersion in hot water or heating in an oven]

[0038] Hereinafter, the substrate layer 11 composed of a polyamide film having a hot water shrinkage rate of less than 5% at 95°C and a thermal shrinkage rate of 4 to 16% at 180°C will be referred to as "substrate layer 11a", and the substrate layer 11 composed of a polyester film having a hot water shrinkage rate of less than 5% at 95°C and a thermal shrinkage rate of 10 to 25% at 180°C will be referred to as "substrate layer 11b", and they will be described separately.

[0039] (Base material layer 11a)

[0040] Regarding the packaging material 10, the 95°C hot water shrinkage rate of the polyamide film constituting the base layer 11a is less than 5%, so that when exposed to heat and / or an electrolyte, the base layer 11a and the metal foil layer 14 can be suppressed from peeling for a long time. In addition, from the viewpoint of being able to further suppress the peeling between the base layer 11a and the metal foil layer 14 for a long time, the 95°C hot water shrinkage rate of the polyamide film is preferably 4% or less. In addition, from the same viewpoint, the 95°C hot water shrinkage rate of the polyamide film is preferably 0% or more.

[0041] In addition, regarding the packaging material 10, by having a 180°C heat shrinkage rate of the polyamide film constituting the substrate layer 11a of 4% or more, the deep drawing formability can be improved, and the forming depth that can be deep drawn can be increased without breaking the adhesive layer 13 and the metal foil layer 14. In addition, from the viewpoint of further improving the deep drawing formability, the 180°C heat shrinkage rate of the polyamide film is preferably 5% or more. On the other hand, regarding the packaging material 10, by having a 180°C heat shrinkage rate of the polyamide film constituting the substrate layer 11a of 16% or less, when exposed to heat and / or an electrolyte, it is possible to suppress the peeling between the substrate layer 11a and the metal foil layer 14 for a long time. In addition, it is possible to prevent the generation of heat wrinkles due to heat shrinkage caused by the heat applied during manufacturing.

[0042] From the viewpoint of obtaining more excellent deep draw formability, the base material layer 11 a is preferably a layer composed of a biaxially stretched polyamide film.

[0043] Examples of the polyamide resin constituting the biaxially stretched polyamide film include nylon 6, nylon 6,6, copolymers of nylon 6 and nylon 6,6, nylon 6,10, poly(m-xylylene adipamide) (MXD6), nylon 11, and nylon 12. Among these, nylon 6 (ONy) is preferred from the viewpoint of excellent heat resistance, puncture strength, and impact strength.

[0044] Examples of the stretching method for the biaxially stretched film include sequential biaxial stretching, tubular biaxial stretching, and simultaneous biaxial stretching. From the viewpoint of obtaining better deep drawing formability, the biaxially stretched film is preferably a film stretched by tubular biaxial stretching.

[0045] The thickness of the substrate layer 11a is preferably 6 to 40 μm, more preferably 10 to 30 μm. When the thickness of the substrate layer 11a is 6 μm or more, there is a tendency to improve the pinhole resistance and insulation of the packaging material 10 for a storage device. If the thickness of the substrate layer 11a exceeds 40 μm, the total thickness of the packaging material 10 for a storage device becomes large, and sometimes the capacity of the battery must be reduced, which is not preferred.

[0046] (Base material layer 11b)

[0047] Regarding the packaging material 10, the 95°C hot water shrinkage rate of the polyester film constituting the base layer 11b is less than 5%, so that when exposed to heat and / or an electrolyte, peeling between the base layer 11b and the metal foil layer 14 can be suppressed for a long time. In addition, from the viewpoint of being able to suppress peeling between the base layer 11b and the metal foil layer 14 for a longer period of time, the 95°C hot water shrinkage rate of the polyester film is preferably 4% or less. In addition, from the same viewpoint, the 95°C hot water shrinkage rate of the polyester film is preferably 0% or more.

[0048] In addition, regarding the packaging material 10, the 180°C heat shrinkage rate of the polyester film constituting the base layer 11b is 10% or more, so that deep drawing formability can be improved, and the forming depth that can be deep drawn can be increased without breaking the adhesive layer 13 and the metal foil layer 14. On the other hand, regarding the packaging material 10, the 180°C heat shrinkage rate of the polyester film constituting the base layer 11b is 25% or less, so that when exposed to heat and / or electrolyte, the base layer 11b and the metal foil layer 14 can be suppressed from peeling for a long time. In addition, the generation of heat wrinkles due to heat shrinkage caused by heat applied during manufacturing can be prevented.

[0049] From the viewpoint of obtaining more excellent deep draw formability, the base material layer 11 b is preferably a layer composed of a biaxially stretched polyester film.

[0050] Examples of the polyester resin constituting the biaxially stretched polyester film include polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, and copolyesters.

[0051] As the stretching method of the biaxially stretched film, for example, a sequential biaxial stretching method, a tubular biaxial stretching method, a simultaneous biaxial stretching method, etc. can be listed. From the viewpoint of obtaining a more excellent deep drawing formability, the biaxially stretched film is preferably a film stretched by the tubular biaxial stretching method and the simultaneous biaxial stretching method.

[0052] The thickness of the base layer 11b is preferably 6 to 40 μm, more preferably 10 to 30 μm. When the thickness of the base layer 11b is 6 μm or more, there is a tendency to improve the pinhole resistance and insulation of the packaging material 10 for a storage device. If the thickness of the base layer 11b exceeds 40 μm, the total thickness of the packaging material 10 for a storage device becomes large, and sometimes the capacity of the battery must be reduced, which is not preferred.

[0053] (Adhesion-promoting treatment layer 12)

[0054] The easy-adhesion treatment layer 12 is provided on one side of the substrate layer 11 and is disposed between the substrate layer 11 and the adhesive layer 13. The easy-adhesion treatment layer 12 is a layer for improving the adhesion between the substrate layer 11 and the adhesive layer 13, and further improving the adhesion between the substrate layer 11 and the metal foil layer 14. The easy-adhesion treatment layer 12 may not be provided in the packaging material 10 for a storage battery device. In this case, in order to improve the adhesion between the substrate layer 11 and the adhesive layer 13, and further improve the adhesion between the substrate layer 11 and the metal foil layer 14, the surface of the substrate layer 11 on the adhesive layer 13 side may be subjected to a corona treatment.

[0055] The easy-adhesion treatment layer 12 is preferably a layer containing at least one resin selected from the group consisting of polyester resin, acrylic resin, polyurethane resin, epoxy resin and acrylic graft polyester resin. For example, a coating agent containing at least one resin selected from the group consisting of polyester resin, acrylic resin, polyurethane resin, epoxy resin and acrylic graft polyester resin as a main component can be applied on one side of the base layer 11 to form the easy-adhesion treatment layer 12.

[0056] <Polyester resin>

[0057] As the polyester resin, from the viewpoint of adhesiveness, a copolyester in which a copolymer component is introduced to lower the glass transition temperature is preferably used. From the viewpoint of coating properties, the copolyester is preferably water-soluble or water-dispersible. As such a copolyester, a copolyester bonded with at least one group selected from the group consisting of a sulfonic acid group or an alkali metal base thereof (hereinafter referred to as a "sulfonic acid group-containing copolyester") is preferably used.

[0058] Here, the sulfonic acid group-containing copolyester refers to a polyester in which at least one group selected from the group consisting of sulfonic acid groups or alkali metal bases thereof is bonded to a part of a dicarboxylic acid component or a diol component, and preferably a copolyester prepared by using an aromatic dicarboxylic acid component in a ratio of 2 to 10 mol % relative to the total acid components, wherein the aromatic dicarboxylic acid component contains at least one group selected from the group consisting of a sulfonic acid group or an alkali metal base thereof.

[0059] As an example of such a dicarboxylic acid, 5-sodium sulfoisophthalic acid is preferred. In this case, as other dicarboxylic acid components, terephthalic acid, isophthalic acid, phthalic acid, p-β-oxyethoxybenzoic acid, 2,6-naphthalenedicarboxylic acid, 4,4'-dicarboxybiphenyl, 4,4'-dicarboxybenzophenone, bis(4-carboxyphenyl)ethane, adipic acid, sebacic acid, cyclohexane-1,4-dicarboxylic acid, etc. can be cited.

[0060] As the diol component for producing the sulfonic acid group-containing copolyester, ethylene glycol is mainly used, and other diols that can be used include propylene glycol, butylene glycol, neopentyl glycol, diethylene glycol, cyclohexanedimethanol, ethylene oxide adducts of bisphenol A, polyethylene glycol, polypropylene glycol, polytetramethylene glycol, etc. Among them, ethylene glycol, propylene glycol, butylene glycol, neopentyl glycol, diethylene glycol, cyclohexanedimethanol, etc. are preferably used as copolymerization components from the viewpoint of improving compatibility with polystyrene sulfonate.

[0061] In addition, as the polyester resin, a modified polyester copolymer may be used, for example, a block copolymer or a graft copolymer modified by polyester, urethane, epoxy, etc. In the present embodiment, in order to improve the adhesion between the easy-adhesion treatment layer 12 and the base layer 11 and the adhesive layer 13, the easy-adhesion treatment layer 12 may further contain a resin other than the polyester resin. Examples of such resins include urethane resins and acrylic resins.

[0062] <Acrylic resin>

[0063] As the monomer components constituting the acrylic resin, for example, alkyl acrylates, alkyl methacrylates (the alkyl group includes methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, 2-ethylhexyl, lauryl, octadecyl, cyclohexyl, phenyl, benzyl, phenethyl, etc.); hydroxyl-containing monomers such as 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl acrylate, 2-hydroxypropyl methacrylate; acrylamide, methacrylamide, N-methylacrylamide, N-methylmethacrylamide, Monomers containing amide groups such as N-hydroxymethyl acrylamide, N-hydroxymethyl methacrylamide, N,N-dimethylol acrylamide, N-methoxymethyl acrylamide, N-methoxymethyl methacrylamide, and N-phenyl acrylamide; monomers containing amino groups such as N,N-diethylaminoethyl acrylate and N,N-diethylaminoethyl methacrylate; monomers containing epoxy groups such as glycidyl acrylate and glycidyl methacrylate; monomers containing carboxyl groups or salts thereof such as acrylic acid, methacrylic acid, and their salts (lithium salts, sodium salts, potassium salts, etc.). These can be used alone or in combination of two or more. In addition, these can be used in combination with other monomers other than the above.

[0064] As other monomers, for example, monomers containing epoxy groups such as allyl glycidyl ether, monomers containing sulfonic acid groups or salts thereof such as styrene sulfonic acid, vinyl sulfonic acid and their salts (lithium salts, sodium salts, potassium salts, ammonium salts, etc.), monomers containing carboxyl groups or salts thereof such as crotonic acid, itaconic acid, maleic acid, fumaric acid and their salts (lithium salts, sodium salts, potassium salts, ammonium salts, etc.), monomers containing acid anhydrides such as maleic anhydride and itaconic anhydride, vinyl isocyanate, allyl isocyanate, styrene, vinyl methyl ether, vinyl ethyl ether, vinyl trialkoxysilane, alkyl maleic acid monoester, alkyl fumaric acid monoester, acrylonitrile, methacrylonitrile, alkyl itaconic acid monoester, vinylidene chloride, vinyl acetate, vinyl chloride, etc. In addition, as acrylic resins, modified acrylic copolymers such as block copolymers and graft copolymers modified with polyester, urethane, epoxy, etc. can be used.

[0065] The glass transition temperature (Tg) of the acrylic resin used in the present embodiment is not particularly limited, but is preferably 0 to 90° C., and more preferably 10 to 80° C. If the Tg is low, the adhesion under high temperature and high humidity will be reduced, and if the Tg is high, cracks will be generated during stretching. Therefore, from the viewpoint of suppressing these undesirable situations, the Tg of the acrylic resin is preferably within the above range.

[0066] In addition, the weight average molecular weight of the acrylic resin used in the present embodiment is preferably 100,000 or more, and more preferably 300,000 or more. If the weight average molecular weight is low, the moisture and heat resistance will be reduced. In the present embodiment, in order to improve the adhesion between the easy-bonding treatment layer 12 and the substrate layer 11 and the adhesive layer 13, the easy-bonding treatment layer 12 may further contain a resin other than acrylic resin. As such resin, polyester resin, urethane resin, etc. may be cited.

[0067] <Polyurethane resin>

[0068] As the polyurethane resin, a water-based polyurethane resin is preferably used. As the water-based polyurethane resin, a self-emulsifying type is preferably used from the viewpoint of small particle size and good stability. The particle size of the water-based polyurethane is preferably formed to be about 10 to 100 nm. For the water-based polyurethane resin used in this embodiment, its glass transition temperature (Tg) is preferably 40 to 150°C. If Tg is above 40°C, there is a tendency to fully suppress the occurrence of adhesion when it is rolled into a roll after coating. On the other hand, if Tg is too high compared to the drying temperature after coating, it is difficult to form a uniform film, so Tg is preferably below 150°C.

[0069] In addition, in the present embodiment, a crosslinking agent can also be used together with the water-based polyurethane. As a crosslinking agent for water-based polyurethane, a general water-soluble crosslinking agent such as a water-soluble epoxy compound can be used. A water-soluble epoxy compound is a compound having solubility in water and having more than two epoxy groups. As a water-soluble epoxy compound, for example, polyepoxides obtained by etherification of glycols such as 1 mole of ethylene glycol, diethylene glycol, triethylene glycol, polyethylene glycol, propylene glycol, dipropylene glycol, tripropylene glycol, polypropylene glycol, 1,4-butanediol, 1,6-hexanediol, and neopentyl glycol with 2 moles of epichlorohydrin; and diepoxides obtained by esterification of dicarboxylic acids such as 1 mole of phthalic acid, terephthalic acid, adipic acid, and oxalic acid with 2 moles of epichlorohydrin. However, water-soluble epoxy compounds are not limited to these.

[0070] These water-soluble crosslinking agents crosslink with the water-based polyurethane resin, thereby improving the water resistance and solvent resistance of the coating film, and helping to improve the adhesion between the easy-adhesion treatment layer 12 and the substrate layer 11 and the adhesive layer 13. In this embodiment, in order to improve the adhesion between the easy-adhesion treatment layer 12 and the substrate layer 11 and the adhesive layer 13, it can also contain a resin other than the urethane resin. As such resins, (for example) polyester resins, acrylic resins, etc. can be listed.

[0071] In addition, the easy-adhesion treatment layer 12 can also be constituted in the following manner, for example: containing the above-mentioned resin as a main component; and a curing agent such as a polyfunctional isocyanate, a polyfunctional glycidyl compound, and a melamine-based compound. In this way, by containing the above-mentioned resin as a main component and a curing agent such as a polyfunctional isocyanate, a polyfunctional glycidyl compound, and a melamine-based compound, a cross-linking structure can be introduced, thereby forming a strong easy-adhesion treatment layer 12.

[0072] The coating agent used to form the easy-adhesion treatment layer 12 can be a solvent system or an aqueous system. For the dispersed type (dispersion system) using an aqueous main agent, its molecular weight is relatively large, which can increase the cohesive force between molecules, thereby being effective for the adhesion between the easy-adhesion treatment layer 12 and the substrate layer 11 and the adhesive layer 13.

[0073] The thickness of the easy-adhesion treatment layer 12 is preferably 0.02 to 0.5 μm, and more preferably 0.04 to 0.3 μm. If the thickness of the easy-adhesion treatment layer 12 is 0.02 μm or more, it is easy to form a uniform easy-adhesion treatment layer 12, thereby tending to obtain a more sufficient easy-adhesion effect. On the other hand, if the thickness of the easy-adhesion treatment layer 12 is 0.5 μm or less, there is a tendency to further improve the deep drawing formability of the packaging material 10.

[0074] (Adhesive layer 13)

[0075] The adhesive layer 13 is a layer for bonding the base layer 11 and the metal foil layer 14. The adhesive layer 13 and the base layer 11 are bonded via the easy-bonding treatment layer 12. The adhesive layer 13 has the adhesion required to strongly bond the base layer 11 and the metal foil layer 14, and also has the followability to suppress the breakage of the metal foil layer 14 caused by the base layer 11 during cold forming (even if the component is deformed or stretched, it will not peel off, so that the adhesive layer 13 is reliably formed on the component).

[0076] As the adhesive constituting the adhesive layer 13, for example, a two-component curing polyurethane adhesive can be used, which has a main agent containing a polyol such as polyester polyol, polyether polyol, acrylic polyol, and a curing agent containing an aromatic or aliphatic isocyanate. In the above adhesive, the molar ratio of the isocyanate group of the curing agent to the hydroxyl group of the main agent (=NCO / OH) is preferably 1 to 10, and more preferably 2 to 5.

[0077] The polyurethane adhesive can be aged at 40° C. for 4 days or more after application to allow the hydroxyl group of the main agent to react with the isocyanate group of the curing agent, thereby making the base material layer 11 and the metal foil layer 14 more firmly bonded.

[0078] From the viewpoint of obtaining desired adhesive strength, followability, processability, and the like, the thickness of the adhesive layer 13 is preferably 1 to 10 μm, and more preferably 2 to 6 μm.

[0079] (Metal foil layer 14)

[0080] As the metal foil layer 14, various metal foils such as aluminum and stainless steel can be cited. From the perspective of processability such as moisture resistance and ductility, and cost, the metal foil layer 14 is preferably aluminum foil. The aluminum foil may be a general soft aluminum foil, and from the perspective of excellent pinhole resistance and ductility during molding, an iron-containing aluminum foil is preferred.

[0081] In the aluminum foil containing iron (100 mass%), the iron content is preferably 0.1 to 9.0 mass%, more preferably 0.5 to 2.0 mass%. When the iron content is 0.1 mass% or more, a packaging material 10 having better pinhole resistance and ductility can be obtained. When the iron content is 9.0 mass% or less, a packaging material 10 having better flexibility can be obtained.

[0082] In addition, as the aluminum foil, soft aluminum foil subjected to annealing treatment (for example, aluminum foil composed of 8021 material or 8079 material in JIS standard) is more preferable from the viewpoint of providing desired ductility during molding.

[0083] The metal foil used for the metal foil layer 14 is preferably subjected to a degreasing treatment, for example, in order to obtain the desired electrolyte resistance. In addition, in order to simplify the manufacturing process, the metal foil is preferably a metal foil whose surface is not etched. As the degreasing treatment, for example, a wet degreasing treatment or a dry degreasing treatment can be adopted, but from the viewpoint of simplifying the manufacturing process, a dry degreasing treatment is preferred.

[0084] As the dry degreasing treatment, for example, a method of performing the degreasing treatment by extending the treatment time in the step of annealing the metal foil can be cited. Sufficient electrolyte resistance can also be obtained by performing the degreasing treatment simultaneously with the annealing treatment for softening the metal foil.

[0085] In addition, as the above-mentioned dry degreasing treatment, a treatment other than the above-mentioned annealing treatment, such as a flame treatment and a corona treatment, etc. In addition, as the above-mentioned dry degreasing treatment, for example, the following degreasing treatment can be adopted, that is, active oxygen generated when the metal foil is irradiated with ultraviolet rays of a specific wavelength is used to oxidatively decompose and remove the contaminants.

[0086] As the above-mentioned wet degreasing treatment, (for example) acid degreasing treatment or alkaline degreasing treatment can be used. As the acid used in the above-mentioned acid degreasing treatment, (for example) inorganic acids such as sulfuric acid, nitric acid, hydrochloric acid, and hydrofluoric acid can be used. These acids can be used alone or in combination of two or more. In addition, as the alkali used in the alkaline degreasing treatment, (for example) sodium hydroxide with a high etching effect can be used. In addition, the alkaline degreasing treatment can also be carried out using a material doped with a weak alkaline substance or a surfactant. The wet degreasing treatment described above can be carried out by (for example) an immersion method or a spray method.

[0087] The thickness of the metal foil layer 14 is preferably 9 to 200 μm, more preferably 15 to 150 μm, and further preferably 15 to 100 μm from the viewpoint of barrier properties, pinhole resistance, and processability. When the thickness of the metal foil layer 14 is 9 μm or more, it is not easy to break even if stress is applied due to molding. When the thickness of the metal foil layer 14 is 200 μm or less, the increase in mass of the packaging material can be reduced, and the decrease in the weight energy density of the storage device can be suppressed.

[0088] (Anti-corrosion treatment layers 15a, 15b)

[0089] The anti-corrosion treatment layers 15a and 15b play a role in suppressing the corrosion of the metal foil layer 14 caused by the electrolyte or the hydrofluoric acid generated by the reaction of the electrolyte and water. In addition, the anti-corrosion treatment layer 15a volatilizes to improve the adhesion between the metal foil layer 14 and the adhesive layer 13. In addition, the anti-corrosion treatment layer 15b plays a role in improving the adhesion between the metal foil layer 14 and the sealant adhesive layer 16. The anti-corrosion treatment layer 15a and the anti-corrosion treatment layer 15b may be layers of the same composition or layers of different compositions.

[0090] The anti-corrosion treatment layers 15a and 15b can be formed by (for example) the following method, namely, subjecting the layer of the base material to become the anti-corrosion treatment layers 15a and 15b to degreasing treatment, hot water conversion treatment, anodizing treatment, chemical conversion treatment, coating with a coating agent having anti-corrosion ability, or a combination of these treatments.

[0091] Among the above-mentioned treatments, the degreasing treatment, the hot water conversion treatment, and the anodizing treatment (especially the hot water conversion treatment and the anodizing treatment) are treatments in which the surface of the metal foil (aluminum foil) is dissolved with a treatment agent to form a metal compound (aluminum compound (boehmite, aluminum oxide)) with excellent corrosion resistance. Therefore, such treatments may be included in the definition of chemical conversion treatment because they form a co-continuous structure from the metal foil layer 14 to the anti-corrosion treatment layers 15a and 15b.

[0092] As degreasing treatment, acid degreasing and alkali degreasing can be listed. As acid degreasing, the following acid degreasing method can be listed, which is obtained by using the above-mentioned sulfuric acid, nitric acid, hydrochloric acid, hydrofluoric acid and other inorganic acids alone or by mixing them. In addition, as acid degreasing, by using an acid degreasing agent formed by dissolving a fluorine-containing compound such as monosodium ammonium difluoride using the above-mentioned inorganic acid, not only the degreasing effect of the metal foil layer 14 is achieved, but also a passive metal fluoride can be formed, which is effective in terms of hydrofluoric acid resistance. As alkali degreasing, a method using sodium hydroxide and the like can be listed.

[0093] As the above-mentioned hot water conversion treatment, for example, boehmite treatment obtained by immersing the metal foil layer 14 in boiling water added with triethanolamine can be adopted. As the above-mentioned anodic oxidation treatment, for example, acid-proof aluminum treatment can be adopted. In addition, as the above-mentioned chemical conversion treatment, for example, chromate treatment, zirconium treatment, titanium treatment, vanadium treatment, molybdenum treatment, calcium phosphate treatment, strontium hydroxide treatment, cerium treatment, ruthenium treatment, or a combination of two or more of these can be adopted. For these hot water conversion treatments, anodic oxidation treatments, and chemical conversion treatments, it is preferred to implement the above-mentioned degreasing treatment in advance.

[0094] It should be noted that the chemical conversion treatment is not limited to the wet method, and a method in which the treatment agent used in the treatment is mixed with the resin component and then applied may be adopted. In addition, the anti-corrosion treatment is preferably a coating type chromate treatment from the viewpoint of maximizing its effect and treating waste liquid.

[0095] As the coating agent used in the coating type anticorrosion treatment of applying a coating agent having anticorrosion performance, there can be cited a coating agent containing at least one selected from the group consisting of rare earth element oxide sol, anionic polymer, and cationic polymer. The method using a coating agent containing a rare earth element oxide sol is particularly preferred.

[0096] The method using a coating agent containing a rare earth element oxide sol is a pure coating type anti-corrosion treatment, and by using this method, even a general coating method can provide an anti-corrosion effect to the metal foil layer 14. In addition, the layer formed using the rare earth element oxide sol has the anti-corrosion effect (inhibitor effect) of the metal foil layer 14 and is also a suitable material from an environmental point of view.

[0097] In the rare earth element oxide sol, microparticles of rare earth element oxide (for example, particles with an average particle size of 100 nm or less) are dispersed in a liquid dispersion medium. Examples of rare earth element oxides include cerium oxide, yttrium oxide, neodymium oxide, and lanthanum oxide. Among them, cerium oxide is preferred. In this way, the adhesion with the metal foil layer 14 can be further improved. As the liquid dispersion medium of the rare earth element oxide sol, various solvents such as water, alcohol solvents, hydrocarbon solvents, ketone solvents, ester solvents, and ether solvents can be used. Among them, water is preferred. The rare earth element oxides contained in the anti-corrosion treatment layers 15a and 15b can be used alone or in combination of two or more.

[0098] In order to stabilize the dispersion of rare earth oxide particles, the rare earth oxide sol preferably contains inorganic acids such as nitric acid, hydrochloric acid, phosphoric acid, acetic acid, malic acid, ascorbic acid, lactic acid, and their salts as dispersion stabilizers. Among these dispersion stabilizers, phosphoric acid or phosphates are particularly preferably used. Thus, the following effects can be expected: not only the dispersion and stabilization of rare earth oxide particles, but also in the use of packaging materials for lithium ion batteries, the chelating ability of phosphoric acid is used to improve the adhesion with the metal foil layer 14, the electrolyte resistance is imparted by capturing the metal ions dissolved by the influence of hydrofluoric acid (passive formation), and the cohesion of the rare earth oxide layer caused by the dehydration condensation of phosphoric acid even at low temperatures is improved. As phosphoric acid or phosphates that can be used as dispersion stabilizers, (for example) orthophosphoric acid, pyrophosphoric acid, metaphosphoric acid, their alkali metal salts, ammonium salts, etc. can be listed. Among them, condensed phosphoric acids such as trimetaphosphoric acid, tetrametaphosphoric acid, hexametaphosphoric acid, and supermetaphosphoric acid or their alkali metal salts and ammonium salts are preferred for the functional manifestation as a packaging material for lithium ion batteries. In particular, if the dry film-forming properties (drying capacity, heat) when using a coating composition containing a rare earth element oxide sol and various coating methods to form a layer containing a rare earth oxide are considered, a reagent with excellent reactivity at low temperatures is preferred, and sodium salts are preferred from the perspective of excellent dehydration condensation at low temperatures. As a phosphate, a water-soluble salt is preferred. The phosphoric acid or phosphate contained in the anti-corrosion treatment layer 15a, 15b can be used alone or in combination of two or more.

[0099] In the rare earth element oxide sol, the amount of phosphoric acid or its salt is preferably 1 part by mass or more, more preferably 5 parts by mass or more, relative to 100 parts by mass of the rare earth element oxide. If it is 1 part by mass or more, the sol is well stabilized and it is easy to satisfy the function as a packaging material for lithium ion batteries. The upper limit of the amount of phosphoric acid or its salt relative to 100 parts by mass of the rare earth element oxide is within the range that does not cause a decrease in the function of the rare earth element oxide sol. The upper limit is preferably 100 parts by mass or less, more preferably 50 parts by mass or less, and further preferably 20 parts by mass or less, relative to 100 parts by mass of the rare earth element oxide.

[0100] However, since the layer formed by the rare earth element oxide sol is an aggregate of inorganic particles, the cohesive force of the layer itself is low even after the drying and curing step. Therefore, in order to supplement the cohesive force of the layer, it is preferably compounded with an anionic polymer.

[0101] Examples of the anionic polymer include polymers having a carboxyl group, such as poly(meth)acrylic acid (or its salt), or copolymers obtained by copolymerizing poly(meth)acrylic acid as a main component. Examples of the copolymer components of the copolymer include the following monomers: (meth)acrylic acid alkyl ester monomers (alkyl groups are methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, 2-ethylhexyl, and cyclohexyl); (meth)acrylamide, N-alkyl (meth)acrylamide, N,N-dialkyl (meth)acrylamide (alkyl groups are methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, 2-ethylhexyl, and cyclohexyl); N-alkoxy (meth)acrylamide, N,N-dialkoxy (meth)acrylamide (alkoxy The monomers containing the amide group include methoxy, ethoxy, butoxy and isobutoxy, etc.), N-hydroxymethyl (meth) acrylamide and N-phenyl (meth) acrylamide; hydroxyl group-containing monomers such as 2-hydroxyethyl (meth) acrylate and 2-hydroxypropyl (meth) acrylate; glycidyl (meth) acrylate and allyl glycidyl ether; silane-containing monomers such as (meth) acryloxypropyl trimethoxysilane and (meth) acryloxypropyl triethoxysilane; isocyanate-containing monomers such as (meth) acryloxypropyl isocyanate, etc. In addition, styrene, α-methylstyrene, vinyl methyl ether, vinyl ethyl ether, maleic acid, maleic acid alkyl monoester, fumaric acid, fumaric acid alkyl monoester, itaconic acid, itaconic acid alkyl monoester, (meth) acrylonitrile, vinylidene chloride, ethylene, propylene, vinyl chloride, vinyl acetate, butadiene, etc. can be listed.

[0102] The anionic polymer plays a role in improving the stability of the anti-corrosion treatment layer 15a, 15b (oxide layer) obtained using the rare earth element oxide sol. This is achieved through the following effects, namely, the effect of protecting the hard and brittle oxide layer by the acrylic resin component, and the effect of capturing (cation trap) ion pollutants (especially sodium ions) from the phosphate contained in the rare earth element oxide sol. That is, in the anti-corrosion treatment layer 15a, 15b obtained using the rare earth element oxide sol, especially if alkali metal ions such as sodium or alkaline earth metal ions are contained, the performance of the anti-corrosion treatment layer 15a, 15b is prone to deterioration starting from the place containing the ions. Therefore, by fixing the sodium ions and the like contained in the rare earth element oxide sol with the help of the anionic polymer, the durability of the anti-corrosion treatment layer 15a, 15b is improved.

[0103] The anti-corrosion treatment layers 15a and 15b obtained by combining anionic polymers and rare earth element oxide sols have the same anti-corrosion performance as the anti-corrosion treatment layers 15a and 15b formed by applying chromate treatment to the metal foil layer 14. The anionic polymer is preferably a structure obtained by cross-linking a substantially water-soluble polyanionic polymer. As a cross-linking agent for forming the structure, compounds having an isocyanate group, a glycidyl group, a carboxyl group and an oxazoline group can be cited. A silane coupling agent can also be further used to introduce a cross-linking site having a siloxane bond.

[0104] Examples of the compound having an isocyanate group include diisocyanates such as toluene diisocyanate, xylylene diisocyanate or its hydride, hexamethylene diisocyanate, 4,4'-diphenylmethane diisocyanate or its hydride, and isophorone diisocyanate; or polyisocyanates such as adducts obtained by reacting these isocyanates with polyols such as trimethylolpropane, biuret bodies obtained by reacting with water, or isocyanurate bodies as trimers; or blocked polyisocyanates obtained by blocking these polyisocyanates with alcohols, lactams, oximes, and the like.

[0105] Examples of the compound having a glycidyl group include epoxy compounds formed by reacting epichlorohydrin with diols such as ethylene glycol, diethylene glycol, triethylene glycol, polyethylene glycol, propylene glycol, dipropylene glycol, tripropylene glycol, polypropylene glycol, 1,4-butanediol, 1,6-hexanediol, and neopentyl glycol; epoxy compounds formed by reacting epichlorohydrin with polyols such as glycerol, polyglycerol, trimethylolpropane, pentaerythritol, and sorbitol; and epoxy compounds formed by reacting epichlorohydrin with dicarboxylic acids such as phthalic acid, terephthalic acid, oxalic acid, and adipic acid.

[0106] Examples of the compound having a carboxyl group include various aliphatic or aromatic dicarboxylic acids. In addition, poly(meth)acrylic acid or an alkali (earth) metal salt of poly(meth)acrylic acid may also be used.

[0107] Examples of the compound having an oxazoline group include, for example, a low molecular weight compound having two or more oxazoline units, or a compound obtained by copolymerizing a polymerizable monomer such as isopropenyl oxazoline with an acrylic monomer such as (meth)acrylic acid, alkyl (meth)acrylate, or hydroxyalkyl (meth)acrylate.

[0108] Examples of the silane coupling agent include γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltriethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-chloropropylmethoxysilane, vinyltrichlorosilane, γ-mercaptopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-β(aminoethyl)-γ-aminopropyltrimethoxysilane, and γ-isocyanatepropyltriethoxysilane. In particular, epoxysilane, aminosilane, and isocyanatesilane are preferred when the reactivity with anionic polymers is taken into consideration.

[0109] The amount of the crosslinking agent is preferably 1 to 50 parts by mass, more preferably 10 to 20 parts by mass, relative to 100 parts by mass of the anionic polymer. If the ratio of the crosslinking agent is 1 part by mass or more relative to 100 parts by mass of the anionic polymer, a crosslinked structure is easily formed sufficiently. If the ratio of the crosslinking agent is 50 parts by mass or less relative to 100 parts by mass of the anionic polymer, the pot life of the coating solution is improved.

[0110] The method of crosslinking the anionic polymer is not limited to the above-mentioned crosslinking agent, and may be a method of forming ionic crosslinks using titanium or zirconium compounds, etc. In addition, these materials can be applied to the coating composition forming the anticorrosion treatment layer 15a.

[0111] In the above-described anti-corrosion treatment layers 15a and 15b, in order to form an inclined structure with the metal foil layer 14, the anti-corrosion treatment layers 15a and 15b obtained by chemical conversion treatment represented by chromate treatment are formed in the following manner: the metal foil layer 14 is treated with a chemical conversion treatment agent containing hydrofluoric acid, hydrochloric acid, nitric acid, sulfuric acid or salts thereof, and then the metal foil layer 14 is reacted with chromium or a non-chromium compound to form a chemical conversion treatment layer on the metal foil layer 14. However, since the above-mentioned chemical conversion treatment uses an acid in the chemical conversion treatment agent, it is accompanied by deterioration of the working environment or corrosion of the coating device.

[0112] On the other hand, unlike chemical conversion treatment represented by chromate treatment, the aforementioned coating type anti-corrosion treatment layers 15a and 15b do not need to form an inclined structure with respect to the metal foil layer 14. Therefore, the properties of the coating agent are not restricted by acidity, alkalinity, or neutrality, and a good working environment can be achieved. In addition, from the viewpoint that an alternative to chromate treatment using a chromium compound is needed in terms of environmental hygiene, the coating type anti-corrosion treatment layers 15a and 15b are preferred.

[0113] If necessary, the anticorrosion treatment layers 15a and 15b may further form a laminated structure laminated with a cationic polymer. Examples of the cationic polymer include polyethyleneimine, an ionic polymer complex composed of polyethyleneimine and a polymer having a carboxylic acid, a primary amine-grafted acrylic resin in which a primary amine is grafted onto an acrylic main skeleton, polyallylamine or derivatives thereof, and an aminophenol resin.

[0114] Examples of the "polymer having carboxylic acid" that forms the ionic polymer complex include, for example, polycarboxylic acid (salt), copolymers obtained by introducing a comonomer into a polycarboxylic acid (salt), polysaccharides having a carboxyl group, and the like. Examples of the polycarboxylic acid (salt) include, for example, polyacrylic acid or its ionic salt. Examples of the polysaccharides having a carboxyl group include, for example, carboxymethyl cellulose or its ionic salt. Examples of the ionic salt include, for example, alkali metal salts, alkaline earth metal salts, and the like.

[0115] The primary amine grafted acrylic resin is a resin obtained by grafting a primary amine onto an acrylic main skeleton. Examples of the acrylic main skeleton include various monomers used in the above-mentioned acrylic polyols, such as poly(meth)acrylic acid. Examples of the primary amine grafted onto the acrylic main skeleton include ethyleneimine and the like.

[0116] As polyallylamine or its derivatives, homopolymers or copolymers of allylamine, allylamine amide sulfate, diallylamine, dimethylallylamine, etc. can be used, and then, with regard to these amines, free amine and the stabilized product formed with acetic acid or hydrochloric acid can be used. In addition, as further copolymer components, maleic acid, sulfur dioxide, etc. can also be used. And then the type that thermal crosslinking property is given by methoxylating the primary amine part can also be used. These cationic polymers can use one alone, and two or more can also be used in combination. As cationic polymers, among the above, preferably at least one selected from the group consisting of polyallylamine and its derivatives.

[0117] The cationic polymer is preferably used in combination with a crosslinking agent having a functional group such as a carboxyl group or a glycidyl group that can react with an amine / imine. As a crosslinking agent used in combination with the cationic polymer, a polymer having a carboxylic acid that forms an ionic polymer complex with polyethyleneimine can also be used, and examples thereof include (for example) polycarboxylic acids (salts) such as polyacrylic acid or its ionic salts, or copolymers into which comonomers are introduced, and polysaccharides having carboxyl groups such as carboxymethylcellulose or its ionic salts.

[0118] In the present embodiment, cationic polymer is also recorded as a constituent element for forming anticorrosion treatment layer 15a, 15b. The reason is that various compounds are used to conduct in-depth research in order to impart electrolyte resistance and hydrofluoric acid resistance required by lithium ion battery packaging materials, and it is found that cationic polymer itself can also be a compound imparting electrolyte resistance and hydrofluoric acid resistance. The main reason is presumably because fluorine ions (anion traps) are captured by cationic groups, thereby suppressing the damage of metal foil layer 14. In addition, cationic polymer is also very preferred in terms of improving the adhesion of anticorrosion treatment layer 15b and sealant adhesive layer 16. In addition, cationic polymer is water-soluble in the same way as the aforementioned anionic polymer, so a cross-linked structure is formed by using the above-mentioned cross-linking agent, thereby improving water resistance. In this way, even if a cationic polymer is used, a cross-linked structure can be formed, so when rare earth oxide sol is used for the formation of anticorrosion treatment layer 15a, 15b, as its protective layer, a cationic polymer can also be used instead of the above-mentioned anionic polymer.

[0119] As can be seen from the above, examples of combinations of the above-mentioned coating-type anticorrosion treatment include: (1) only rare earth oxide sol; (2) only anionic polymer; (3) only cationic polymer; (4) rare earth oxide sol + anionic polymer (laminated composite); (5) rare earth oxide sol + cationic polymer (laminated composite); (6) (rare earth oxide sol + anionic polymer: laminated composite) / cationic polymer (multilayer); (7) (rare earth oxide sol + cationic polymer: laminated composite) / anionic polymer (multilayer), etc. Among these, (1) and (4) to (7) are preferred, and (4) to (7) are more preferred. In addition, in the case of the anticorrosion treatment layer 15a, (6) is particularly preferred because it can further achieve the anticorrosion effect and the anchoring effect (adhesion improvement effect). In addition, in the case of the anti-corrosion treatment layer 15b, since it becomes easier to maintain the electrolyte resistance on the side of the sealant layer 17, (6) and (7) are particularly preferred. However, the present embodiment is not limited to the above combination. For example, as an example of the selection of the anti-corrosion treatment, from the viewpoint of good adhesion with the modified polyolefin resin listed in the description of the sealant adhesive layer 16 described later, a cationic polymer is a very preferred material. Therefore, in the case where the sealant adhesive layer 16 is composed of a modified polyolefin resin, there can be a design in which a cationic polymer is provided on the surface in contact with the sealant adhesive layer 16 (for example, a configuration such as configurations (5) and (6)).

[0120] However, the anti-corrosion treatment layers 15a and 15b are not limited to the above-mentioned layers. For example, as the coating type chromate as a known technology, it can also be formed by using a treatment agent formed by mixing phosphoric acid and a chromium compound in a resin binder (aminophenol resin, etc.). If this treatment agent is used, a layer having both anti-corrosion function and tight adhesion can be formed. In addition, for the above-mentioned chemical conversion treatment layer (a layer formed by degreasing treatment, hot water conversion treatment, anodizing treatment, chemical conversion treatment or a combination of these treatments), in order to improve the tight adhesion, the above-mentioned cationic polymer and / or anionic polymer can also be used to implement a composite treatment, or for the combination of these treatments, the cationic polymer and / or anionic polymer can be stacked as a multilayer structure. In addition, although it is necessary to consider the stability of the coating liquid, a coating agent formed by previously liquefying a rare earth oxide sol and a cationic polymer or anionic polymer in a single component (one liquefaction) can be used to form a layer having both anti-corrosion function and tight adhesion.

[0121] The mass per unit area of ​​the anticorrosion treatment layers 15a and 15b is preferably 0.005 to 0.200 g / m 2 In the range of 0.010 to 0.100 g / m 2If the mass per unit area is 0.005 g / m 2 If the above mass per unit area exceeds 0.200 g / m 2 , the anti-corrosion function is saturated and will not change much. On the other hand, when using rare earth oxide sol, if the coating is thick, the curing by heat during drying becomes insufficient, and there is a concern that the cohesive force will decrease. It should be noted that the above content is recorded in terms of mass per unit area, but if the specific gravity is known, the thickness can also be converted from it.

[0122] From the viewpoint of the anticorrosion function and the function as an anchoring agent, the thickness of the anticorrosion treatment layers 15a and 15b is, for example, preferably 10 nm to 5 μm, and more preferably 20 nm to 500 nm.

[0123] (Sealing agent bonding layer 16)

[0124] The sealant adhesive layer 16 is a layer that bonds the metal foil layer 14 formed with the anticorrosion treatment layer 15b to the sealant layer 17. Depending on the adhesive component forming the sealant adhesive layer 16, the packaging material 10 is roughly divided into a heat lamination structure and a dry lamination structure.

[0125] The adhesive component forming the sealant adhesive layer 16 in the heat lamination structure is preferably an acid-modified polyolefin resin obtained by grafting and modifying a polyolefin resin with an acid. In the acid-modified polyolefin resin, since a polar group is introduced into a part of the non-polar polyolefin resin, the sealant layer 17 composed of a non-polar polyolefin resin film and the anti-corrosion treatment layer 15b, which is mostly polar, can be tightly bonded. In addition, by using an acid-modified polyolefin resin, the resistance of the packaging material 10 to contents such as an electrolyte is improved, and even if hydrofluoric acid is generated inside the battery, it is easy to prevent the reduction in adhesion caused by the deterioration of the sealant adhesive layer 16.

[0126] Examples of polyolefin resins as acid-modified polyolefin resins include, for example, low-density, medium-density and high-density polyethylenes; ethylene-α-olefin copolymers; polypropylene; and propylene-α-olefin copolymers. Polyolefin resins in the form of copolymers may be block copolymers or random copolymers. In addition, as polyolefin resins, copolymers obtained by copolymerizing the above-mentioned substances with polar molecules such as acrylic acid or methacrylic acid, or polymers such as cross-linked polyolefins may also be used. Examples of acids for modifying polyolefin resins include carboxylic acids, epoxy compounds, and acid anhydrides, preferably maleic anhydride. The acid-modified polyolefin resins used in the sealant adhesive layer 16 may be one type or two or more types.

[0127] The heat-laminated sealant adhesive layer 16 can be formed by extruding the above-mentioned adhesive component using an extruder. The thickness of the heat-laminated sealant adhesive layer 16 is preferably 2 to 50 μm.

[0128] As the adhesive component forming the sealant adhesive layer 16 of the dry lamination structure, for example, the same adhesive as exemplified for the adhesive layer 13 can be cited. In this case, in order to suppress swelling caused by the electrolyte or hydrolysis caused by hydrofluoric acid, it is preferred to design the composition of the adhesive so that the main agent has a skeleton that is not easily hydrolyzed and the crosslinking density can be increased.

[0129] In order to increase the crosslink density, for example, dimer fatty acids, esters or hydrides of dimer fatty acids, reduced diols of dimer fatty acids, and reduced diols of esters or hydrides of dimer fatty acids may be added to the adhesive. The dimer fatty acids are acids obtained by dimerizing various unsaturated fatty acids, and their structures include acyclic, monocyclic, polycyclic, and aromatic ring types.

[0130] The fatty acid as the starting material of the dimer fatty acid is not particularly limited. In addition, it is also possible to use this dimer fatty acid as the main component and introduce a dibasic acid such as that used in general polyester polyols. As a curing agent for the main agent constituting the sealant adhesive layer 16, an isocyanate compound that can also be used as a chain extender for polyester polyols can be used (for example). Thus, the crosslinking density of the adhesive film is improved, resulting in improved solubility or swelling, and simultaneously, due to the increased concentration of carbamate groups, it is also possible to expect an improvement in substrate adhesion.

[0131] Since the sealant adhesive layer 16 formed by dry lamination has highly hydrolyzable bonding sites such as ester groups and urethane groups, in applications requiring higher reliability, it is preferable to use an adhesive component formed by heat lamination as the sealant adhesive layer 16. For example, the sealant adhesive layer 16 is formed by adding the above-mentioned various curing agents to a coating liquid prepared by dissolving or dispersing an acid-modified polyolefin resin in a solvent such as toluene or methylcyclohexane (MCH), applying the coating liquid, and drying the coating liquid.

[0132] When the sealant adhesive layer 16 is formed by extrusion molding, the adhesive resin is easily oriented in the MD direction (machine direction) due to the stress generated during the extrusion molding. In this case, in order to alleviate the anisotropy of the sealant adhesive layer 16, an elastomer may be blended into the sealant adhesive layer 16. As the elastomer blended into the sealant adhesive layer 16, for example, an olefin elastomer, a styrene elastomer, etc. can be used.

[0133] The average particle size of the elastomer is preferably such that the compatibility between the elastomer and the adhesive resin is improved and the anisotropy of the sealant adhesive layer 16 is relaxed. Specifically, the average particle size of the elastomer is preferably, for example, 200 nm or less.

[0134] It should be noted that the average particle size of the elastomer can be obtained, for example, by taking an enlarged photograph of a cross section of the elastomer composition using an electron microscope and then measuring the average particle size of the dispersed crosslinked rubber component by image analysis. The above-mentioned elastomers may be used alone or in combination of two or more.

[0135] When the elastomer is blended into the sealant adhesive layer 16, the blending amount of the elastomer added to the sealant adhesive layer 16 (100 mass %) is preferably, for example, 1 to 25 mass %, and more preferably 10 to 20 mass %. By setting the blending amount of the elastomer to 1 mass % or more, there is a tendency that the effect of alleviating the anisotropy of the sealant adhesive layer 16 can be improved while improving the compatibility with the adhesive resin. In addition, by setting the blending amount of the elastomer to 25 mass % or less, there is a tendency that the effect of suppressing the swelling of the sealant adhesive layer 16 due to the electrolyte can be improved.

[0136] As the sealant adhesive layer 16 , for example, a dispersed adhesive resin liquid in which an adhesive resin is dispersed in an organic solvent may be used.

[0137] As for the thickness of the sealant adhesive layer 16, in the case of a hot lamination structure, it is preferably 8 μm or more and 50 μm or less, and more preferably 20 μm or more and 40 μm or less. By having a thickness of the sealant adhesive layer 16 of 8 μm or more, it is easy to obtain sufficient bonding strength between the metal foil layer 14 and the sealant layer 17, and by being 50 μm or less, it is easy to reduce the amount of moisture in the battery element that penetrates from the end surface of the packaging material to the inside. In addition, as for the thickness of the sealant adhesive layer 16, in the case of a dry lamination structure, it is preferably 1 μm or more and 5 μm or less. By having a thickness of the sealant adhesive layer 16 of 1 μm or more, it is easy to obtain sufficient bonding strength between the metal foil layer 14 and the sealant layer 17, and by being 5 μm or less, the generation of cracks in the sealant adhesive layer 16 can be suppressed.

[0138] (Sealing agent layer 17)

[0139] The sealant layer 17 is a layer that imparts sealing properties to the packaging material 10 by heat sealing, that is, a layer that is arranged inside and heat-fused when the power storage device is assembled. As the sealant layer 17, a resin film composed of a polyolefin resin or an acid-modified polyolefin resin obtained by graft-modifying a polyolefin resin with an acid such as maleic anhydride can be cited. Among them, a polyolefin resin that can improve the barrier properties of water vapor and form the shape of the power storage device without excessive deformation due to heat sealing is preferred, and polypropylene is particularly preferred.

[0140] Examples of polyolefin resins include low-density, medium-density, and high-density polyethylenes; ethylene-α-olefin copolymers; polypropylene; and propylene-α-olefin copolymers. The polyolefin resin used as a copolymer may be a block copolymer or a random copolymer. These polyolefin resins may be used alone or in combination of two or more.

[0141] In addition, low-crystalline ethylene-butene copolymers, low-crystalline propylene-butene copolymers, terpolymers composed of copolymers of the three components of ethylene, butene and propylene, anti-blocking agents (AB agents) such as silica, zeolite, acrylic resin beads, and fatty acid amide-based lubricants can also be added to the above-mentioned types of polypropylene, that is, random polypropylene, homopolypropylene, and block polypropylene.

[0142] Examples of the acid-modified polyolefin-based resin include the same resins as those exemplified for the sealant adhesive layer 16 .

[0143] The sealant layer 17 may be a single layer film or a multilayer film, and may be selected according to the desired function. For example, in order to provide moisture resistance, a multilayer film in which a resin such as ethylene-cyclic olefin copolymer and polymethylpentene is inserted may be used.

[0144] In addition, the sealant layer 17 may contain various additives such as a flame retardant, a slip agent, an anti-blocking agent, an antioxidant, a light stabilizer, and an adhesion-imparting agent.

[0145] When a heat-fusible film formed by extrusion molding is used as the sealant layer 17, there is a tendency to orient in the extrusion direction of the heat-fusible film. Therefore, from the viewpoint of alleviating the anisotropy of the sealant layer 17 caused by orientation, an elastomer may be blended into the heat-fusible film. As a result, when the recessed portion is formed by cold molding the packaging material 10 for a storage device, the sealant layer 17 can be prevented from whitening.

[0146] As the elastomer constituting the sealant layer 17, for example, the same material as the material exemplified as the elastomer constituting the sealant adhesive layer 16 can be used. In the case where the sealant layer 17 is a multilayer film structure, it can also be configured in the following manner: at least one of the plurality of layers constituting the multilayer film structure contains an elastomer. For example, in the case where the sealant layer 17 has a three-layer stacked structure consisting of a stacked random polypropylene layer / block polypropylene layer / random polypropylene layer, the elastomer may be blended only in the block polypropylene layer, only in the random polypropylene layer, or in both the random polypropylene layer and the block polypropylene layer.

[0147] In addition, in order to give the sealant layer 17 smoothness, it may also contain a slip agent. In this way, when the recessed portion is formed in the power storage device packaging material 10 by cold forming, the sealant layer 17 contains a slip agent, which can prevent the side or corner of the recessed portion with a high elongation rate in the power storage device packaging material 10 from being overstretched. As a result, it is possible to prevent the metal foil layer 14 and the sealant adhesive layer 16 from peeling off, or to prevent the sealant layer 17 and the sealant adhesive layer 16 from breaking or whitening due to cracks.

[0148] When the sealant layer 17 contains a slip agent, the content of the slip agent in the sealant layer 17 (100 mass%) is preferably 0.001 mass % to 0.5 mass %. If the content of the slip agent is 0.001 mass % or more, there is a tendency to further suppress the whitening of the sealant layer 17 during cold forming. In addition, if the content of the slip agent is 0.5 mass % or less, there is a tendency to suppress the decrease in the adhesion strength between the surface of the sealant layer 17 and the surface of the other layer in contact therewith.

[0149] The thickness of the sealant layer 17 is preferably 10 to 100 μm, more preferably 20 to 60 μm. When the thickness of the sealant layer 17 is 20 μm or more, sufficient heat sealing strength can be obtained, and when the thickness is 90 μm or less, the amount of water vapor infiltration from the end of the packaging material can be reduced.

[0150] [Method for producing packaging material]

[0151] Next, a method for producing the sealing material 10 will be described. It should be noted that the method for producing the sealing material 10 is not limited to the following method.

[0152] As a method for producing the packaging material 10 , for example, there can be mentioned a method having the following steps S11 to S14 .

[0153] Step S11 : a step of forming the anti-corrosion treatment layer 15 a on one surface of the metal foil layer 14 and forming the anti-corrosion treatment layer 15 b on the other surface of the metal foil layer 14 .

[0154] Step S12: a step of forming an easy-adhesion treatment layer 12 on one surface of the base material layer 11 to obtain a laminated body.

[0155] Step S13: A step of bonding the surface of the anticorrosion treated layer 15 a facing the metal foil layer 14 and the surface of the laminate on the easy-adhesion treated layer 12 side via the adhesive layer 13 .

[0156] Step S14 : a step of forming a sealant layer 17 on the surface of the anticorrosion treated layer 15 b on the side opposite to the metal foil layer 14 via the sealant adhesive layer 16 .

[0157] (Step S11)

[0158] In step S11, an anti-corrosion treatment layer 15a is formed on one side of the metal foil layer 14, and an anti-corrosion treatment layer 15b is formed on the other side of the metal foil layer 14. The anti-corrosion treatment layers 15a and 15b can be formed separately, or both can be formed at once. Specifically, for example, by applying an anti-corrosion treatment agent (the base material of the anti-corrosion treatment layer) on both sides of the metal foil layer 14, and then drying, curing, and sintering are performed in sequence, so as to form the anti-corrosion treatment layers 15a and 15b at once. In addition, an anti-corrosion treatment agent can be applied on one side of the metal foil layer 14, and then dried, cured, and sintered in sequence. After the anti-corrosion treatment layer 15a is formed, the anti-corrosion treatment layer 15b is similarly formed on the other side of the metal foil layer 14. The formation order of the anti-corrosion treatment layers 15a and 15b is not particularly limited. In addition, regarding the anti-corrosion treatment agent, different anti-corrosion treatment agents can be used in the anti-corrosion treatment layer 15a and the anti-corrosion treatment layer 15b, or the same anti-corrosion treatment agent can be used. As the above-mentioned anticorrosion treatment agent, for example, an anticorrosion treatment agent for coating type chromate treatment can be used. The coating method of the anticorrosion treatment agent is not particularly limited, and can be, for example, a gravure coating method, a gravure reverse coating method, a roll coating method, a reverse roll coating method, a die coating method, a rod coating method, a kiss coating method, a comma coating method, etc. It should be noted that as the metal foil layer 14, an untreated metal foil layer can be used, and a metal foil layer that has been degreased by a wet degreasing treatment or a dry degreasing treatment can also be used.

[0159] (Step S12)

[0160] In step S12, an easy-adhesion treatment layer 12 is formed on one side of the substrate layer 11. Here, as an example of a method for forming the easy-adhesion treatment layer 12, an inline coating method is described. First, an aqueous coating liquid containing a dispersion is prepared, and the dispersion is formed by dispersing the above-mentioned resin as the main component of the easy-adhesion treatment layer 12 with a dispersant. Next, the above-mentioned aqueous coating liquid is applied to one side of the thermoplastic resin film (the base material of the substrate layer 11) before the crystal orientation is completed. Next, the applied aqueous coating liquid is dried, and thereafter, the thermoplastic resin film is stretched in at least one axial direction.

[0161] Next, the orientation of the thermoplastic resin film is completed by heat treatment, thereby obtaining a laminate having an easy-adhesion treatment layer 12 formed on one side of the substrate layer 11. By forming the easy-adhesion treatment layer 12 by using this in-line coating method, the adhesion between the substrate layer 11 and the easy-adhesion treatment layer 12 can be improved. It should be noted that the method for forming the easy-adhesion treatment layer 12 is not limited to the above method, and any method can be used. In addition, the time point for forming the easy-adhesion treatment layer 12 is not limited to the present embodiment.

[0162] (Step S13)

[0163] In step S13, the surface of the anticorrosion treatment layer 15a opposite to the metal foil layer 14 and the surface of the laminate on the side of the easy-adhesion treatment layer 12 are bonded together by dry lamination or the like using an adhesive for forming the adhesive layer 13. In step S13, an aging (curing) treatment may be performed in a range of room temperature to 100° C. in order to promote adhesion. The aging time is, for example, 1 to 10 days.

[0164] (Step S14)

[0165] After step S13, a sealant layer 17 is formed on the surface of the anti-corrosion treatment layer 15b of the laminated body formed by sequentially laminating the base material layer 11, the easy-adhesion treatment layer 12, the adhesive layer 13, the anti-corrosion treatment layer 15a, the metal foil layer 14 and the anti-corrosion treatment layer 15b, via the sealant adhesive layer 16. The sealant layer 17 can be laminated by dry lamination and sandwich lamination, or can be laminated together with the sealant adhesive layer 16 by coextrusion. From the viewpoint of improving adhesion, the sealant layer 17 is preferably laminated by sandwich lamination (for example), or laminated together with the sealant adhesive layer 16 by coextrusion, and more preferably laminated by sandwich lamination.

[0166] Through the above-described steps S11 to S14, the encapsulating material 10 is obtained. It should be noted that the order of steps in the method for manufacturing the encapsulating material 10 is not limited to the method of sequentially implementing the above-described steps S11 to S14. The order of the implemented steps can be appropriately changed, for example, step S11 can be performed after step S12.

[0167] [Electricity storage device]

[0168] Next, a power storage device having a packaging material 10 as a container is described. The power storage device comprises: a battery element 1 including an electrode, a lead 2 extending from the electrode, and a container for accommodating the battery element 1, wherein the container is formed by the packaging material 10 for the power storage device with the sealant layer 17 on the inner side. The container can be obtained by overlapping two packaging materials in a manner that the sealant layers 17 face each other, and heat-melting the peripheral portions of the overlapping packaging materials 10, or by folding back and overlapping one packaging material, and similarly heat-melting the peripheral portions of the packaging material 10. In addition, the power storage device can have a packaging material 20 as a container. Examples of the power storage device include (for example) secondary batteries such as lithium-ion batteries, nickel-hydrogen batteries, and lead storage batteries, and electrochemical capacitors such as double-layer capacitors.

[0169] The lead 2 is sandwiched and sealed by the sealing material 10 which forms a container with the sealant layer 17 as the inner side. The lead 2 may be sandwiched by the sealing material 10 via a tab sealant.

[0170] [Method for manufacturing power storage device]

[0171] Next, a method for manufacturing an electric storage device using the above-mentioned packaging material 10 will be described. It should be noted that here, a case where a secondary battery 40 is manufactured using the embossed packaging material 30 will be described as an example. Figure 2 FIG. 1 is a diagram showing the embossed type sealing material 30 . Figure 3 (a) to (d) are perspective views showing the manufacturing steps of a single-side molded battery using the packaging material 10. As the secondary battery 40, a double-side molded battery can also be manufactured by providing two packaging materials such as embossed packaging materials 30, and bonding such packaging materials to each other while adjusting the alignment. In addition, the embossed packaging material 30 can be formed using the packaging material 10.

[0172] The secondary battery 40 as a single-side molded battery can be manufactured through, for example, the following steps S21 to S25 .

[0173] Step S21: a step of preparing a packaging material 10, a battery element 1 including electrodes, and leads 2 extending from the electrodes.

[0174] Step S22: A step of forming a concave portion 32 for arranging the battery element 1 on one side of the packaging material 10 (see Figure 3 (a) and Figure 3 (b)).

[0175] Step S23: a step of placing the battery element 1 in the molding process area (recess 32) of the embossed packaging material 30, folding the embossed packaging material 30 so that the cover 34 covers the recess 32 and overlapping, and heat-sealing one side of the embossed packaging material 30 under pressure so as to clamp the lead 2 extending from the battery element 1 (see Figure 3 (b) and Figure 3 (c)).

[0176] Step S24: leaving one side other than the side holding the lead 2, pressurizing and heat-melting the other sides, then injecting electrolyte from the remaining side, and pressurizing and heat-melting the remaining side under vacuum (refer to Figure 3 (c)).

[0177] Step S25: a step of cutting off the edge portions of the pressurized heat-welded edges other than the edge holding the lead wire 2 and bending them toward the molding region (recess 32) (see Figure 3 (d)).

[0178] (Step S21)

[0179] In step S21, a packaging material 10, a battery element 1 including electrodes, and a lead 2 extending from the electrode are prepared. The packaging material 10 is prepared based on the above-mentioned embodiment. There is no particular limitation on the battery element 1 and the lead 2, and well-known battery elements 1 and leads 2 can be used.

[0180] (Step S22)

[0181] In step S22, a recess 32 for arranging the battery element 1 is formed on the sealant layer 17 side of the packaging material 10. The planar shape of the recess 32 is made to be consistent with the shape of the battery element 1, for example, a rectangular shape when viewed from above. The recess 32 is formed, for example, by pressing a pressing member having a rectangular pressure surface against a portion of the packaging material 10 in its thickness direction. In addition, the pressing position, that is, the recess 32 is formed at a position that is biased from the center of the packaging material 10 cut into a rectangle toward one end of the packaging material 10 in the length direction. Thus, after the molding process, the other end side where the recess 32 is not formed can be folded back to form a cover (cover 34).

[0182] As a method for forming the recess 32, more specifically, there can be exemplified a molding process (deep stamping) using a mold. As a molding method, there can be exemplified a method of using a female mold and a male mold configured to have a gap greater than the thickness of the packaging material 10, and pressing the male mold together with the packaging material 10 into the female mold. By adjusting the amount of pressing of the male mold, the depth (deep stamping amount) of the recess 32 can be adjusted to a desired amount. By forming the recess 32 in the packaging material 10, an embossed packaging material 30 is obtained. The embossed packaging material 30 has, for example, Figure 2 Here, Figure 2 (a) is a three-dimensional view of the embossed packaging material 30; Figure 2 (b) is along Figure 2 (a) is a longitudinal cross-sectional view of the embossed sealing material 30 taken along line bb.

[0183] (Step S23)

[0184] In step S23, a battery element 1 consisting of a positive electrode, a separator, and a negative electrode is arranged in the molding processing area (recess 32) of the embossed packaging material 30. In addition, the lead 2 extending from the battery element 1 and respectively joined to the positive electrode and the negative electrode is led out from the molding processing area (recess 32). Thereafter, the embossed packaging material 30 is folded back at approximately the center of its length direction, and overlapped in a manner that the sealant layers 17 are on the inner side of each other, and one side of the embossed packaging material 30 holding the lead 2 is pressurized and heat-fused. Pressurized heat fusion is controlled by three conditions: temperature, pressure, and time, and can be appropriately set. The temperature of pressurized heat fusion is preferably above the temperature at which the sealant layer 17 melts.

[0185] It should be noted that the thickness of the sealant layer 17 before heat welding is preferably 40% or more and 80% or less relative to the thickness of the lead 2. When the thickness of the sealant layer 17 is above the lower limit, there is a tendency that the heat welding resin can fully fill the end of the lead 2, and when it is below the upper limit, the thickness of the end of the packaging material 10 of the secondary battery 40 can be appropriately suppressed, and the amount of water infiltration from the end of the packaging material 10 can be reduced.

[0186] (Step S24)

[0187] In step S24, one side other than the side holding the lead 2 is left, and the other sides are heat-welded under pressure. Thereafter, electrolyte is injected from the remaining side, and the remaining side is heat-welded under pressure in a vacuum state. The heat-welding conditions are the same as those in step S23.

[0188] (Step S25)

[0189] The peripheral heat-sealed edge portions other than the edges holding the lead 2 are cut off to remove the sealant layer 17 exposed from the edges. Thereafter, the peripheral heat-sealed portion is folded back toward the molding region 32 to form a folded portion 42, thereby obtaining a secondary battery 40.

[0190] Although preferred embodiments of the packaging material for a power storage device and the method for manufacturing a power storage device of the present invention have been described in detail above, the present invention is not limited to the specific embodiments described above, and various modifications and changes can be made within the scope of the gist of the present invention described in the claims.

[0191] [Example]

[0192] Hereinafter, the present invention will be described in more detail based on examples, but the present invention is not limited to the following examples.

[0193] (Preparation of base material layer)

[0194] The following nylon films A-1-1 to A-1-2, B-1-1 to B-1-7, C-1-1 to C-1-3 and D-1-1 to D-1-2 produced by tubular biaxial stretching were prepared as the substrate layer 11. The thickness, 95°C hot water shrinkage and 180°C heat shrinkage of each nylon film are shown below.

[0195] A-1-1: thickness 15 μm, 95°C hot water shrinkage 3.6%, 180°C heat shrinkage 5.3%.

[0196] A-1-2: thickness 15 μm, 95°C hot water shrinkage 2.8%, 180°C heat shrinkage 3.0%.

[0197] B-1-1: thickness 25 μm, 95°C hot water shrinkage 4.0%, 180°C heat shrinkage 4.8%.

[0198] B-1-2: thickness 25 μm, 95°C hot water shrinkage 4.0%, 180°C heat shrinkage 4.8%.

[0199] B-1-3: thickness 25 μm, 95°C hot water shrinkage 3.6%, 180°C heat shrinkage 9.4%.

[0200] B-1-4: thickness 25 μm, 95°C hot water shrinkage 3.7%, 180°C heat shrinkage 15.2%.

[0201] B-1-5: thickness 25 μm, 95°C hot water shrinkage 2.6%, 180°C heat shrinkage 2.7%.

[0202] B-1-6: thickness 25 μm, 95°C hot water shrinkage 7.7%, 180°C heat shrinkage 15.1%.

[0203] B-1-7: thickness 25 μm, 95°C hot water shrinkage 4.8%, 180°C heat shrinkage 20.4%.

[0204] C-1-1: thickness 25 μm, 95°C hot water shrinkage 4.0%, 180°C heat shrinkage 4.8%.

[0205] C-1-2: thickness 25 μm, 95°C hot water shrinkage 3.6%, 180°C heat shrinkage 9.4%.

[0206] C-1-3: thickness 25 μm, 95°C hot water shrinkage 3.7%, 180°C heat shrinkage 15.2%.

[0207] D-1-1: thickness 25 μm, 95°C hot water shrinkage 3.7%, 180°C heat shrinkage 4.5%.

[0208] D-1-2: thickness 25 μm, 95°C hot water shrinkage 2.4%, 180°C heat shrinkage 2.8%.

[0209] (Preparation of coating agent for forming easy-adhesion treatment layer)

[0210] As a coating agent for forming an easily-adhesive treatment layer, a coating agent having the following composition was prepared.

[0211] Coating agent: AQUANATE 100, a self-emulsifying polyisocyanate manufactured by Nihon Polyurethane Industries, Ltd., and SEAHOSTARKE-P30, a spherical silica fine particle (average particle size: 0.3 μm) manufactured by Nippon Shokubai Chemical Industries, Ltd., were added to ARON MELT PES-1000, a water-soluble polyester manufactured by Toagosei Co., Ltd., at a blending ratio (mass ratio) of 95 / 5 / 0.5, and the mixture was diluted with water.

[0212] (Example 1-1)

[0213] In Example 1-1, the packaging material 10 for a power storage device was prepared by the following method. First, a soft aluminum foil 8079 material (manufactured by Toyo Alminium Co., Ltd.) with a thickness of 40 μm was prepared as the metal foil layer 14. Next, a sodium polyphosphate-stabilized cerium oxide sol (anticorrosive treatment agent) adjusted to a solid concentration of 10% by mass using distilled water as a solvent was applied to both sides of the metal foil layer 14 by gravure coating. At this time, the phosphoric acid was 10 parts by mass relative to 100 parts by mass of cerium oxide.

[0214] Next, after the applied sodium polyphosphate stabilized cerium oxide sol is dried, baking treatment is sequentially performed to form an anti-corrosion treatment layer 15a on one side of the metal foil layer 14 and an anti-corrosion treatment layer 15b on the other side of the metal foil layer 14. At this time, as baking conditions, the temperature is set to 150° C. and the treatment time is set to 30 seconds.

[0215] Next, a nylon film A-1-1 was used as the base material layer 11, and one surface of the base material layer 11 was subjected to a corona treatment.

[0216] Next, a polyurethane adhesive was applied as an adhesive layer 13 on the surface of the anticorrosion treatment layer 15a of the metal foil layer 14 on the side opposite to the metal foil layer 14. Next, the metal foil layer 14 was bonded to the corona-treated surface of the base layer 11 via the adhesive layer 13 by dry lamination. Thereafter, an aging treatment was performed by placing the structure consisting of the base layer 11, the adhesive layer 13, the anticorrosion treatment layer 15a, the metal foil layer 14 and the anticorrosion treatment layer 15b in an atmosphere at a temperature of 60°C for 6 days.

[0217] Next, a polyurethane adhesive is applied as a sealant bonding layer 16 on the surface of the anticorrosion treatment layer 15b opposite to the metal foil layer 14. The polyurethane adhesive is obtained by mixing polyisocyanate into an acid-modified polyolefin dissolved in a mixed solvent of toluene and methylcyclohexane. Then, a polyolefin film (a film in which the surface of the sealant bonding layer 16 side of the unstretched polypropylene film is corona-treated) having a thickness of 40 μm, which will become the sealant layer 17, is bonded to the metal foil layer 14 via the sealant bonding layer 16 by a dry lamination method. Thereafter, an aging treatment is performed by placing the structure consisting of the base layer 11, the adhesive layer 13, the anticorrosion treatment layer 15a, the metal foil layer 14, the anticorrosion treatment layer 15b, the sealant bonding layer 16 and the sealant layer 17 in an atmosphere at a temperature of 40°C for 6 days. Thus, a packaging material 10 for a storage device is produced.

[0218] (Comparative Example 1-1)

[0219] In Comparative Example 1-1, a power storage device packaging material 10 was prepared in the same manner as in Example 1-1, except that the base material layer 11 was changed to the nylon film A-1-2.

[0220] <Evaluation of Forming Depth>

[0221] For the packaging material 10 for the storage device produced in Example 1-1 and Comparative Example 1-1, the forming depth that can be deep-drawn is evaluated according to the following method. First, the packaging material 10 for the storage device is arranged in a molding device with the sealant layer 17 facing upward. The molding depth of the molding device is set to 5.0 to 7.5 mm per 0.5 mm, and cold forming is performed in an environment where the room temperature is 23°C and the dew point temperature is -35°C. It should be noted that the die uses a rectangular cross-section of 70mm×80mm, a die radius (RP) of 1.00mm on the bottom, and a die fillet radius (RCP) of 1.00mm on the side. In addition, the die uses a die radius (RD) of 1.00mm on the upper surface of the opening. While illuminating the packaging material 10, visually confirm whether the cold-formed part has fractures and pinholes, and find the maximum value of the forming depth that can be deep-drawn when no fractures or pinholes occur. The results are shown in Table 1.

[0222] <Evaluation of Adhesion>

[0223] For the packaging material 10 for the storage battery device produced in Example 1-1 and Comparative Example 1-1, the adhesion between the substrate layer 11 and the metal foil layer 14 was evaluated by the following method. First, the packaging material 10 for the storage battery device is arranged in a molding device with the sealant layer 17 facing upward. The molding depth of the molding device is set to 5 mm, and cold molding is performed in an environment with a room temperature of 23°C and a dew point temperature of -35°C. It should be noted that the die used has a rectangular cross-section of 70 mm × 80 mm, a die radius (RP) of 1.00 mm on the bottom, and a die corner radius (RCP) of 1.00 mm on the side. In addition, the die used a die having a die radius (RD) of 1.00 mm on the upper surface of the opening.

[0224] Secondly, the cold-formed packaging material 10 is placed in a 100mL beaker containing 30mL of 1M lithium hexafluorophosphate solution (solvent volume ratio = ethyl carbonate: dimethyl carbonate: dimethyl carbonate = 1:1:1). Next, the beaker containing the packaging material 10 is sealed in an 18L square can and exposed to the electrolyte by placing it in a temperature environment of 40°C for 2 hours. After that, the packaging material 10 is taken out from the beaker in the 18L square can, placed in an oven at 110°C, or placed in an environment with a temperature of 60°C and a humidity of 95%, or placed in hot water at 50°C. Then, after 1 week, 2 weeks, 3 weeks and 4 weeks, visually confirm whether there is peeling between the substrate layer 11 and the metal foil layer 14 of the packaging material 10, and find the maximum value (unit: week) during which no peeling is confirmed between the substrate layer 11 and the metal foil layer 14. Based on the results, the adhesion between the base material layer 11 and the metal foil layer 14 was evaluated according to the following evaluation criteria.

[0225] A: No peeling was confirmed even after 4 weeks.

[0226] B: No peeling was observed after 3 weeks, but peeling occurred after 4 weeks.

[0227] C: No peeling was observed after 2 weeks, but peeling occurred after 3 weeks.

[0228] D: No peeling was observed after 1 week, but peeling occurred after 2 weeks.

[0229] E: Delamination occurred after 1 week.

[0230] [Table 1]

[0231]

[0232] From the results shown in Table 1, it can be seen that in the packaging material in which the thickness of the base material layer 11 is 15 μm, the packaging material of Example 1-1 using a polyamide film having a 95°C hot water shrinkage rate of less than 5% and a 180°C thermal shrinkage rate of 4 to 16% as the base material layer 11, it is confirmed that the deep drawing formability can be improved while maintaining tightness, compared with the packaging material of Comparative Example 1-1 using a polyamide film having a 180°C thermal shrinkage rate that does not meet the above conditions.

[0233] (Example 1-2)

[0234] In Example 1-2, a packaging material 10 for a storage device is prepared in the same manner as in Example 1-1, except that: instead of using sodium polyphosphate-stabilized cerium oxide sol to form the anti-corrosion treatment layers 15a and 15b, a treatment solution consisting of a phenolic resin, a chromium fluoride compound and phosphoric acid is applied to both sides of the metal foil layer 14 to form a coating, which is then baked to perform a chromate treatment to form the anti-corrosion treatment layers 15a and 15b, and the substrate layer 11 is changed to a nylon film B-1-1.

[0235] (Example 1-3)

[0236] In Example 1-3, a power storage device packaging material 10 was produced in the same manner as in Example 1-1, except that the base material layer 11 was changed to the nylon film B-1-2.

[0237] (Examples 1-4)

[0238] In Example 1-4, a power storage device packaging material 10 was produced in the same manner as in Example 1-1, except that the base material layer 11 was changed to the nylon film B-1-3.

[0239] (Examples 1-5)

[0240] In Example 1-5, a power storage device packaging material 10 was produced in the same manner as in Example 1-1, except that the base material layer 11 was changed to the nylon film B-1-4.

[0241] (Comparative Example 1-2)

[0242] In Comparative Example 1-2, a power storage device packaging material 10 was prepared in the same manner as in Example 1-1, except that the base material layer 11 was changed to the nylon film B-1-5.

[0243] (Comparative Examples 1-3)

[0244] In Comparative Example 1-3, a power storage device packaging material 10 was prepared in the same manner as in Example 1-1, except that the base material layer 11 was changed to the nylon film B-1-6.

[0245] (Comparative Examples 1-4)

[0246] In Comparative Example 1-4, a power storage device packaging material 10 was prepared in the same manner as in Example 1-1, except that the base material layer 11 was changed to the nylon film B-1-7.

[0247] <Evaluation of molding depth>

[0248] The power storage device packaging materials 10 produced in Examples 1-2 to 1-5 and Comparative Examples 1-2 to 1-4 were evaluated for the depth of deep drawing possible by the same test method as in Example 1-1, etc. The results are shown in Table 2.

[0249] <Evaluation of Adhesion>

[0250] The power storage device packaging materials 10 produced in Examples 1-2 to 1-5 and Comparative Examples 1-2 to 1-4 were evaluated for adhesion between the base material layer 11 and the metal foil layer 14 by the same test method as in Example 1-1.

[0251] [Table 2]

[0252]

[0253] From the results shown in Table 2, it can be seen that in the packaging material in which the thickness of the base material layer 11 is 25 μm, the packaging materials of Examples 1-2 to 1-5 using a polyamide film having a 95°C hot water shrinkage rate of less than 5% and a 180°C thermal shrinkage rate of 4 to 16% as the base material layer 11, compared with the packaging materials of Comparative Examples 1-2 to 1-4 using a polyamide film having at least one of a 95°C hot water shrinkage rate and a 180°C thermal shrinkage rate that does not satisfy the above conditions, it was confirmed that the deep drawing formability can be improved while maintaining good adhesion.

[0254] (Examples 1-6)

[0255] In Example 1-6, the following changes were made to Example 1-1. In Example 1-6, the base material layer 11 was changed to nylon film C-1-1. In addition, the sealant adhesive layer 16 was formed by extruding maleic anhydride-modified polypropylene (manufactured by Mitsui Chemicals, trade name: Admer) which will become the base material of the sealant adhesive layer 16. At this time, the thickness of the sealant adhesive layer 16 was set to 20 μm. In addition, a sandwich lamination method was used instead of a dry lamination method, and a polyolefin film (a film in which the surface of the sealant adhesive layer 16 side of the unstretched polypropylene film was corona treated) with a thickness of 60 μm was bonded (heat-pressed) to the anti-corrosion treated layer 15b via the sealant adhesive layer 16 at 180°C. In Example 1-6, except for the above-mentioned changes, a packaging material 10 for a storage device was prepared in the same manner as in Example 1-1.

[0256] (Examples 1-7)

[0257] In Example 1-7, a power storage device packaging material 10 was produced in the same manner as in Example 1-6, except that the base material layer 11 was changed to the nylon film C-1-2.

[0258] (Example 1-8)

[0259] In Example 1-8, a power storage device packaging material 10 was produced in the same manner as in Example 1-6, except that the base material layer 11 was changed to the nylon film C-1-3.

[0260] <Evaluation of molding depth>

[0261] The power storage device packaging materials 10 produced in Examples 1-6 to 1-8 were evaluated for the depth of deep drawing possible by the same test method as in Example 1-1. The results are shown in Table 3.

[0262] <Evaluation of Adhesion>

[0263] The adhesiveness between the base material layer 11 and the metal foil layer 14 was evaluated for the power storage device packaging materials 10 produced in Examples 1-6 to 1-8 by the same test method as in Example 1-1 and the like.

[0264] [Table 3]

[0265]

[0266] From the results shown in Table 3, it can be seen that in the packaging material with a thickness of the base material layer 11 of 25 μm, for the packaging materials of Examples 1-6 to 1-8 using a polyamide film with a hot water shrinkage rate of less than 5% at 95°C and a thermal shrinkage rate of 4 to 16% at 180°C as the base material layer 11, it was confirmed that the deep drawing formability can be improved while maintaining the tightness even when the sealant adhesive layer 16 is provided by the sandwich lamination method.

[0267] (Example 1-9)

[0268] In Example 1-9, a packaging material 10 for a storage device was prepared in the same manner as in Example 1-1, except that an easy-adhesion treatment layer 12 was formed on the surface of the substrate layer 11 on the adhesive layer 13 side, instead of corona treatment on one side of the substrate layer 11, and the substrate layer 11 was changed to nylon film D-1-1. The easy-adhesion treatment layer 12 was coated by an in-line coating method to a solid content of 0.1 g / m 2 A coating agent that is to be a base material of the easy-adhesion treatment layer 12 is applied to one surface of the base layer 11 in a manner and dried, thereby forming the easy-adhesion treatment layer 12 having a thickness of about 0.1 μm.

[0269] (Comparative Examples 1-6)

[0270] In Comparative Example 1-6, a power storage device packaging material 10 was prepared in the same manner as in Example 1-9, except that the base material layer 11 was changed to the nylon film D-1-2.

[0271] <Evaluation of molding depth>

[0272] The power storage device packaging materials 10 produced in Example 1-9 and Comparative Example 1-6 were evaluated for the depth of deep drawing possible by the same test method as in Example 1-1, etc. The results are shown in Table 4.

[0273] <Evaluation of Adhesion>

[0274] The adhesiveness between the base material layer 11 and the metal foil layer 14 was evaluated for the power storage device packaging materials 10 produced in Example 1-9 and Comparative Example 1-6 by the same test method as in Example 1-1 and the like.

[0275] [Table 4]

[0276]

[0277] From the results shown in Table 4, it can be seen that in the packaging material in which the thickness of the base material layer 11 is 25 μm and an easy-adhesion treatment layer 12 is provided, the packaging materials of Examples 1-9 using a polyamide film having a 95°C hot water shrinkage rate of less than 5% and a 180°C thermal shrinkage rate of 4 to 16% as the base material layer 11, compared with the packaging materials of Comparative Examples 1-6 using a polyamide film having a 180°C thermal shrinkage rate that does not meet the above conditions, it is confirmed that the deep drawing formability can be improved while maintaining tightness.

[0278] (Preparation of base material layer)

[0279] The following polyethylene terephthalate films A-2-1 to A-2-2, B-2-1 to B-2-7, and C-2-1 to C-2-2 produced by a simultaneous biaxial stretching method were prepared as the base material layer 11. The thickness, 95°C hot water shrinkage rate, and 180°C heat shrinkage rate of each polyethylene terephthalate film are shown below.

[0280] A-2-1: thickness 12 μm, 95°C hot water shrinkage 3.5%, 180°C heat shrinkage 18.7%.

[0281] A-2-2: thickness 12 μm, 95°C hot water shrinkage 2.5%, 180°C heat shrinkage 6.0%.

[0282] B-2-1: thickness 25 μm, 95°C hot water shrinkage 2.8%, 180°C heat shrinkage 19.9%.

[0283] B-2-2: thickness 25 μm, 95°C hot water shrinkage 2.8%, 180°C heat shrinkage 19.9%.

[0284] B-2-3: thickness 25 μm, 95°C hot water shrinkage 3.3%, 180°C heat shrinkage 23.8%.

[0285] B-2-4: thickness 25 μm, 95°C hot water shrinkage 2.4%, 180°C heat shrinkage 11.2%.

[0286] B-2-5: thickness 25 μm, 95°C hot water shrinkage 2.6%, 180°C heat shrinkage 5.7%.

[0287] B-2-6: thickness 25 μm, 95°C hot water shrinkage 8.5%, 180°C heat shrinkage 19.0%.

[0288] B-2-7: thickness 25 μm, 95°C hot water shrinkage 6.0%, 180°C heat shrinkage 19.9%.

[0289] C-2-1: thickness 25 μm, 95°C hot water shrinkage 2.6%, 180°C heat shrinkage 18.4%.

[0290] C-2-2: thickness 25 μm, 95°C hot water shrinkage 3.1%, 180°C heat shrinkage 6.6%.

[0291] (Preparation of coating agent for forming easy-adhesion treatment layer)

[0292] As a coating agent for forming an easily-adhesive treatment layer, a coating agent having the following composition was prepared.

[0293] Coating agent: AQUANATE 100, a self-emulsifying polyisocyanate manufactured by Nihon Polyurethane Industries, Ltd., and SEAHOSTARKE-P30, a spherical silica fine particle (average particle size: 0.3 μm) manufactured by Nippon Shokubai Chemical Industries, Ltd., were added to ARON MELT PES-1000, a water-soluble polyester manufactured by Toagosei Co., Ltd., at a blending ratio (mass ratio) of 95 / 5 / 0.5, and the mixture was diluted with water.

[0294] (Example 2-1)

[0295] In Example 2-1, the packaging material 10 for a power storage device was prepared by the following method. First, a soft aluminum foil 8079 material (manufactured by Toyo Alminium Co., Ltd.) with a thickness of 40 μm was prepared as the metal foil layer 14. Next, a sodium polyphosphate-stabilized cerium oxide sol (anticorrosive treatment agent) adjusted to a solid concentration of 10% by mass using distilled water as a solvent was applied to both sides of the metal foil layer 14 by gravure coating. At this time, the phosphoric acid was 10 parts by mass relative to 100 parts by mass of cerium oxide.

[0296] Next, after the applied sodium polyphosphate stabilized cerium oxide sol is dried, baking treatment is sequentially performed to form an anti-corrosion treatment layer 15a on one side of the metal foil layer 14 and an anti-corrosion treatment layer 15b on the other side of the metal foil layer 14. At this time, as baking conditions, the temperature is set to 150° C. and the treatment time is set to 30 seconds.

[0297] Next, a polyethylene terephthalate film A-2-1 was used as the base layer 11 , and one surface of the base layer 11 was subjected to a corona treatment.

[0298] Next, a polyurethane adhesive was applied as an adhesive layer 13 on the surface of the anticorrosion treatment layer 15a of the metal foil layer 14 on the side opposite to the metal foil layer 14. Next, the metal foil layer 14 was bonded to the corona-treated surface of the base layer 11 via the adhesive layer 13 by dry lamination. Thereafter, an aging treatment was performed by placing the structure consisting of the base layer 11, the adhesive layer 13, the anticorrosion treatment layer 15a, the metal foil layer 14 and the anticorrosion treatment layer 15b in an atmosphere at a temperature of 60°C for 6 days.

[0299] Next, a sealant adhesive layer 16 is formed on the surface of the anti-corrosion treatment layer 15b opposite to the metal foil layer 14. At this time, the sealant adhesive layer 16 is formed by extruding maleic anhydride-modified polypropylene (manufactured by Mitsui Chemicals, trade name: Admer) which will become the base material of the sealant adhesive layer 16. At this time, the thickness of the sealant adhesive layer 16 is set to 20 μm. Next, a polyolefin film (a film on the side of the sealant adhesive layer 16 of the unstretched polypropylene film) with a thickness of 60 μm is bonded (heated and pressed) to the anti-corrosion treatment layer 15b at 180°C through the sealant adhesive layer 16 to become the sealant layer 17 by a sandwich lamination method. Thus, a packaging material 10 for a storage device is produced.

[0300] (Comparative Example 2-1)

[0301] In Comparative Example 2-1, a power storage device packaging material 10 was prepared in the same manner as in Example 2-1, except that the base material layer 11 was changed to the polyethylene terephthalate film A-2-2.

[0302] <Evaluation of molding depth>

[0303] For the packaging material 10 for the storage device produced in Example 2-1 and Comparative Example 2-1, the forming depth that can be deep-drawn is evaluated according to the following method. First, the packaging material 10 for the storage device is arranged in a molding device with the sealant layer 17 facing upward. The molding depth of the molding device is set to 4.5 to 7.5 mm per 0.5 mm, and cold forming is performed in an environment where the room temperature is 23°C and the dew point temperature is -35°C. It should be noted that the die uses a rectangular cross-section of 70mm×80mm, a die radius (RP) of 1.00mm on the bottom, and a die fillet radius (RCP) of 1.00mm on the side. In addition, the die uses a die radius (RD) of 1.00mm on the upper surface of the opening. While illuminating the packaging material 10, visually confirm whether the cold-formed part has fractures and pinholes, and find the maximum value of the forming depth that can be deep-drawn when no fractures or pinholes occur. The results are shown in Table 5. In the table, “<4.5” means that at least one of a break and a pinhole occurred at a molding depth of 4.5 mm.

[0304] <Evaluation of Adhesion>

[0305] For the packaging material 10 for the storage battery device produced in Example 2-1 and Comparative Example 2-1, the adhesion between the substrate layer 11 and the metal foil layer 14 was evaluated by the following method. First, the packaging material 10 for the storage battery device is arranged in a molding device with the sealant layer 17 facing upward. The molding depth of the molding device is set to 5 mm, and cold molding is performed in an environment with a room temperature of 23°C and a dew point temperature of -35°C. It should be noted that the die used has a rectangular cross-section of 70 mm × 80 mm, a die radius (RP) of 1.00 mm on the bottom, and a die corner radius (RCP) of 1.00 mm on the side. In addition, the die used a die having a die radius (RD) of 1.00 mm on the upper surface of the opening.

[0306] Secondly, the cold-formed packaging material 10 is placed in a 100mL beaker containing 30mL of 1M lithium hexafluorophosphate solution (solvent volume ratio = ethyl carbonate: dimethyl carbonate: dimethyl carbonate = 1:1:1). Next, the beaker containing the packaging material 10 is sealed in an 18L square can and exposed to the electrolyte by placing it in a temperature environment of 40°C for 2 hours. After that, the packaging material 10 is taken out from the beaker in the 18L square can, placed in an oven at 110°C, or placed in an environment with a temperature of 60°C and a humidity of 95%, or placed in hot water at 50°C. Then, after 1 week, 2 weeks, 3 weeks, 4 weeks and 9 weeks, visually confirm whether there is peeling between the substrate layer 11 and the metal foil layer 14 of the packaging material 10, and find the maximum value (unit: week) during which no peeling is confirmed between the substrate layer 11 and the metal foil layer 14. Based on the results, the adhesion between the base material layer 11 and the metal foil layer 14 was evaluated according to the following evaluation criteria. The results are shown in Table 5. When the evaluation is B or higher, it can be said that the adhesion between the base material layer 11 and the metal foil layer 14 is good.

[0307] A: No peeling was confirmed even after 9 weeks.

[0308] B: No delamination was observed after 4 weeks, but delamination occurred after 9 weeks.

[0309] C: No peeling was observed after 3 weeks, but peeling occurred after 4 weeks.

[0310] D: No peeling was observed after 2 weeks, but peeling occurred after 3 weeks.

[0311] E: No peeling was observed after 1 week, but peeling occurred after 2 weeks.

[0312] F: Delamination occurred after 1 week.

[0313] [Table 5]

[0314]

[0315] From the results shown in Table 5, it can be seen that in the packaging material in which the thickness of the base material layer 11 is 12 μm, the packaging material of Example 2-1 using a polyester film having a hot water shrinkage rate of less than 5% at 95°C and a thermal shrinkage rate of 10 to 25% at 180°C as the base material layer 11, it is confirmed that the deep drawing formability can be improved while maintaining tightness, compared with the packaging material of Comparative Example 2-1 using a polyester film having a thermal shrinkage rate at 180°C that does not meet the above conditions.

[0316] (Example 2-2)

[0317] In Example 2-2, the following changes were made to Example 2-1. In Example 2-2, as the sealant adhesive layer 16, a polyurethane adhesive was applied, which was obtained by mixing polyisocyanate into an acid-modified polyolefin dissolved in a mixed solvent of toluene and methylcyclohexane. In addition, a polyolefin film with a thickness of 40 μm (a film in which the surface of the sealant adhesive layer 16 of the unstretched polypropylene film was corona-treated) which will become the sealant layer 17 was bonded to the metal foil layer 14 via the sealant adhesive layer 16 by using a dry lamination method instead of a sandwich lamination method. Then, an aging treatment was performed by placing the structure consisting of the substrate layer 11, the adhesive layer 13, the anti-corrosion treatment layer 15a, the metal foil layer 14, the anti-corrosion treatment layer 15b, the sealant adhesive layer 16 and the sealant layer 17 in an atmosphere at a temperature of 40°C for 6 days. In Example 2-2, a power storage device packaging material 10 was produced in the same manner as in Example 2-1 except for the above-mentioned changes.

[0318] <Evaluation of molding depth>

[0319] The power storage device packaging material 10 produced in Example 2-2 was evaluated for the depth of deep drawing possible by the same test method as in Example 2-1. The results are shown in Table 6.

[0320] <Evaluation of Adhesion>

[0321] The adhesiveness between the base material layer 11 and the metal foil layer 14 was evaluated for the power storage device packaging material 10 produced in Example 2-2 by the same test method as in Example 2-1 and the like.

[0322] [Table 6]

[0323]

[0324] From the results shown in Table 6, it can be seen that in the packaging material in which the thickness of the base material layer 11 is 12 μm, for the packaging material of Example 2-2 using a polyester film having a hot water shrinkage rate of less than 5% at 95°C and a thermal shrinkage rate of 10 to 25% at 180°C as the base material layer 11, it was confirmed that the deep drawing formability can be improved while maintaining the tightness even when the sealant adhesive layer 16 is provided by the dry lamination method.

[0325] (Example 2-3)

[0326] In Example 2-3, a packaging material 10 for a storage device is prepared in the same manner as in Example 2-1, except that: instead of using sodium polyphosphate-stabilized cerium oxide sol to form the anti-corrosion treatment layers 15a and 15b, a treatment solution consisting of a phenolic resin, a chromium fluoride compound and phosphoric acid is applied to both sides of the metal foil layer 14 to form a coating, which is then baked to perform a chromate treatment to form the anti-corrosion treatment layers 15a and 15b, and the substrate layer 11 is changed to a polyethylene terephthalate film B-2-1.

[0327] (Example 2-4)

[0328] In Example 2-4, a power storage device packaging material 10 was produced in the same manner as in Example 2-1, except that the base material layer 11 was changed to the polyethylene terephthalate film B-2-2.

[0329] (Example 2-5)

[0330] In Example 2-5, a power storage device packaging material 10 was produced in the same manner as in Example 2-1, except that the base material layer 11 was changed to the polyethylene terephthalate film B-2-3.

[0331] (Example 2-6)

[0332] In Example 2-6, a power storage device packaging material 10 was produced in the same manner as in Example 2-1, except that the base material layer 11 was changed to the polyethylene terephthalate film B-2-4.

[0333] (Comparative Example 2-2)

[0334] In Comparative Example 2-2, a power storage device packaging material 10 was prepared in the same manner as in Example 2-1, except that the base material layer 11 was changed to the polyethylene terephthalate film B-2-5.

[0335] (Comparative Example 2-3)

[0336] In Comparative Example 2-3, a power storage device packaging material 10 was prepared in the same manner as in Example 2-1, except that the base material layer 11 was changed to the polyethylene terephthalate film B-2-6.

[0337] (Comparative Example 2-4)

[0338] In Comparative Example 2-4, a power storage device packaging material 10 was prepared in the same manner as in Example 2-1, except that the base material layer 11 was changed to the polyethylene terephthalate film B-2-7.

[0339] <Evaluation of molding depth>

[0340] The power storage device packaging materials 10 produced in Examples 2-3 to 2-6 and Comparative Examples 2-2 to 2-4 were evaluated for the depth of deep drawing possible by the same test method as in Example 2-1, etc. The results are shown in Table 7.

[0341] <Evaluation of Adhesion>

[0342] The power storage device packaging materials 10 produced in Examples 2-3 to 2-6 and Comparative Examples 2-2 to 2-4 were evaluated for adhesion between the base material layer 11 and the metal foil layer 14 using the same test method as in Example 2-1.

[0343] [Table 7]

[0344]

[0345] From the results shown in Table 7, it can be seen that in the packaging material in which the thickness of the base material layer 11 is 25 μm, the packaging materials of Examples 2-3 to 2-6 using a polyester film having a 95°C hot water shrinkage rate of less than 5% and a 180°C thermal shrinkage rate of 10 to 25% as the base material layer 11, compared with the packaging materials of Comparative Examples 2-2 to 2-4 using a polyester film having at least one of a 95°C hot water shrinkage rate and a 180°C thermal shrinkage rate that does not satisfy the above conditions, it was confirmed that the deep drawing formability can be improved while maintaining tightness.

[0346] (Example 2-7)

[0347] In Example 2-7, a packaging material 10 for a storage device was prepared in the same manner as in Example 2-1, except that an easy-adhesion treatment layer 12 was formed on the surface of the substrate layer 11 on the adhesive layer 13 side, instead of corona treatment on one side of the substrate layer 11, and the substrate layer 11 was changed to a polyethylene terephthalate film C-2-1. The easy-adhesion treatment layer 12 was coated by an in-line coating method to a solid content of 0.1 g / m 2 A coating agent that is to be a base material of the easy-adhesion treatment layer 12 is applied to one surface of the base layer 11 in a manner and dried, thereby forming the easy-adhesion treatment layer 12 having a thickness of about 0.1 μm.

[0348] (Comparative Example 2-5)

[0349] In Comparative Example 2-5, a power storage device packaging material 10 was prepared in the same manner as in Example 2-7, except that the base material layer 11 was changed to the polyethylene terephthalate film C-2-2.

[0350] <Evaluation of molding depth>

[0351] The power storage device packaging materials 10 produced in Example 2-7 and Comparative Example 2-5 were evaluated for the depth of deep drawing possible by the same test method as in Example 2-1 and the like.

[0352] <Evaluation of Adhesion>

[0353] The adhesiveness between the base material layer 11 and the metal foil layer 14 was evaluated for the power storage device packaging materials 10 produced in Example 2-7 and Comparative Example 2-5 by the same test method as in Example 2-1 and the like.

[0354] [Table 8]

[0355]

[0356] From the results shown in Table 8, it can be seen that in the packaging material in which the thickness of the base material layer 11 is 25 μm and an easy-adhesion treatment layer 12 is provided, the packaging material of Example 2-7 using a polyester film having a 95°C hot water shrinkage rate of less than 5% and a 180°C thermal shrinkage rate of 10 to 25% as the base material layer 11, it is confirmed that the deep drawing formability can be improved while maintaining tightness, compared with the packaging material of Comparative Example 2-5 using a polyester film having a 180°C thermal shrinkage rate that does not meet the above conditions.

[0357] Explanation of symbols

[0358] 1···Battery element; 2···Lead; 10···Packaging material (packaging material for power storage device); 11···Base material layer; 12···Easy-adhesion treatment layer; 13···Adhesive layer; 14···Metal foil layer; 15a, 15b···Anti-corrosion treatment layer; 16···Sealant adhesive layer; 17···Sealant layer; 30···Embossed packaging material; 32···Molding processing area (recess); 34···Lid; 40···Secondary battery.

Claims

1. A packaging material for a power storage device, comprising a structure in which at least a base material layer, an adhesive layer, a metal foil layer, a sealant adhesive layer and a sealant layer are sequentially stacked, It also includes an easy-adhesion treatment layer disposed between the base material layer and the adhesive layer, and first and second anti-corrosion treatment layers disposed on both sides of the metal foil layer. The first and second anti-corrosion treatment layers are formed by zirconium treatment, titanium treatment, vanadium treatment, molybdenum treatment, calcium phosphate treatment, strontium hydroxide treatment, cerium treatment, ruthenium treatment, or a combination of two or more of these treatments, or contain a coating agent selected from the group consisting of rare earth element oxide sol, anionic polymer, and cationic polymer. Only the adhesive layer is stacked between the easy-adhesion treated layer and the first anti-corrosion treated layer, Only the sealant adhesive layer is laminated between the second anticorrosion treatment layer and the sealant layer, The substrate layer is a layer composed of a polyester film having a hot water shrinkage rate of less than 5% at 95°C and a heat shrinkage rate of 10% to 25% at 180°C. The 95°C hot water shrinkage rate is calculated as follows: the substrate layer is cut into a size of 10 cm long x 10 cm wide to obtain a test piece, and the test piece is immersed in 95°C hot water for 30 minutes. The dimensional change rate of the test piece before and after immersion in the longitudinal and transverse directions is calculated based on the following formula (I), and the dimensional change rate in the two directions is calculated as the average value. The 180°C heat shrinkage rate is calculated as follows: the substrate layer is cut into a size of 10 cm long x 10 cm wide to obtain a test piece, and the test piece is heated in an oven at 180°C for 30 minutes. The dimensional change rates of the test piece in the longitudinal and transverse directions before and after heating are calculated based on the following formula (I), and the dimensional change rates in the two directions are calculated as the average value. Dimensional change rate (%) = {(XY) / X}×100···(I) X: the dimension before immersion in hot water or heating in an oven, Y: the dimension after immersion in hot water or heating in an oven.

2. The packaging material for a power storage device according to claim 1, wherein The easy-adhesion treatment layer is a layer containing at least one resin selected from the group consisting of polyester resin, acrylic resin, polyurethane resin, epoxy resin and acrylic graft polyester resin.

3. The packaging material for a power storage device according to claim 1, wherein The anti-corrosion treatment layer comprises: rare earth element oxide; and phosphoric acid or phosphate.

4. The packaging material for a power storage device according to claim 3, wherein The rare earth element oxide is cerium oxide.

5. A power storage device comprising: A battery element comprising electrodes; leads extending from the electrodes; and a container for accommodating the battery element, The container is formed of the packaging material for a power storage device according to any one of claims 1 to 4 so that the sealing compound layer faces inside.

Citation Information

Patent Citations

  • External facing material for power storage device

    JP2013101765A

  • laminate

    JP2014069383A

  • Lithium ion battery outer cover material

    US20130149597A1

  • Packaging material and molded case

    US20150030910A1